Demolding film
By providing a resin layer (A) and a resin layer (B) on the base film of the release film, containing a silicone resin-based and a non-silicon resin-based release agent, the problem of changes in peeling characteristics caused by adhesion during the release film in the prior art is solved, and stable ultralight peeling property is achieved.
Patent Information
- Application Number
- CN202411870382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-03
- Filing Date
- 2023-07-20
- Publication Date
- 2025-04-11
AI Technical Summary
The existing mold release films are prone to change in peeling characteristics due to adhesion during peeling, and it is difficult to achieve stable ultralight peeling properties.
A release film of a specific structure is used, which includes a resin layer (A) on one side of the base film, includes a silicone resin-based release agent, and a resin layer (B) on the other side, including a non-silicon resin-based release agent.
The ultralight peeling property of various adhesives is achieved, while the peeling properties of the release layer are maintained stably, and the peeling force changes caused by adhesion are avoided.
Smart Images

Figure BDA0005195606330000031 
Figure BDA0005195606330000041 
Figure BDA0005195606330000171
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of July 20, 2023, application number 202380013398.X, and invention name “Release Film”. Technical Field
[0002] The present invention relates to a release film, an adhesive sheet and a method for using the adhesive sheet. Background Art
[0003] In the past, release films based on polyester films have excellent properties such as mechanical strength, dimensional stability, chemical resistance, and optical properties, and are excellent in cost performance, so they have been used for various purposes, such as polarizing plates for liquid crystal displays (hereinafter referred to as LCDs), phase difference plates, plasma display panels (hereinafter referred to as PDPs), organic electroluminescent (hereinafter referred to as organic EL), various display components, and other optical uses.
[0004] In recent years, in the use of adhesive layers, durability is sometimes required to be higher than before. For example, when an adhesive layer is used as a component bonding of a touch panel mounted inside a car, the use is outdoor, so it is necessary to firmly bond the components to each other even if they are exposed to a high temperature atmosphere in summer or a low temperature environment in winter. Therefore, as the durability of the adhesive layer itself improves, there is a tendency for the adhesive force of the adhesive layer itself to become stronger than before. Therefore, in the past, the generally used light peeling type release film sometimes becomes difficult to peel off when peeled off from the adhesive layer, requiring further light peeling.
[0005] In addition, as a trend of adhesives in recent years, there is a tendency to prefer adhesive layers with low elastic modulus in terms of better absorption of height difference. When dealing with adhesive layers with low elastic modulus, the surface of the adhesive layer is easily deformed when the release film is peeled off, and sometimes a stringing phenomenon occurs. Therefore, for release films, further light peeling, so-called ultra-light peeling, is required.
[0006] As a countermeasure for ultra-light release of release films, there is a method of increasing the thickness of the release layer to achieve light release. However, if this method is used, depending on the type of release agent to be used, the migrating components from the release layer are transferred to the surface of the adhesive layer, and it may become difficult to obtain the desired adhesive force.
[0007] On the other hand, when a release agent with less mobility is used to suppress the mobility of the release layer, the transfer of the migrating component to the surface of the adhesive layer is reduced, but when the release layer is applied thickly, the slippage of the release layer surface is poor, and when the film is rolled into a roll, the films stick to each other, and there is a problem that the release force of the release layer becomes heavier or the appearance of the release layer surface deteriorates in the lower roll portion of the roll where the film applies pressure. In order to solve this problem, a method of containing microparticles in the release layer to prevent the adhesion of the release film has been studied. (Patent Documents 1, 2).
[0008] As another study, it has been proposed to provide a resin layer containing particles on the surface of a film opposite to the surface on which a release layer is provided (Patent Document 3).
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2004-255704
[0012] Patent Document 2: Japanese Patent Application Publication No. 2017-61081
[0013] Patent Document 3: Japanese Patent Application Publication No. 2016-165825 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] However, if the release layer contains fine particles, adhesion can be prevented, but it is difficult to make the fine particles exist stably on the surface of the release layer, and the release layer itself becomes brittle. As the particles fall off, the release characteristics of the release layer change, and sometimes it is difficult to obtain a stable release force.
[0016] In addition, when a resin layer containing particles is provided on the surface opposite to the surface on which the release layer is provided, adhesion can be prevented. However, depending on the degree of unevenness formed, the unevenness of the particles contained in the resin layer is transferred to the release layer when the film roll is formed, and the release characteristics of the release layer are changed, making it difficult to obtain a stable release force.
[0017] The present invention has been made in view of the above-mentioned actual situation, and aims to provide a release film and a film laminate that achieve ultra-light release properties against various adhesives and in which the release properties of the release layer are not easily changed by blocking.
[0018] Solutions for solving problems
[0019] The present inventors have conducted intensive studies in view of the above-mentioned actual situation and have found that the above-mentioned problems can be solved by using a release film having a specific structure, thereby completing the present invention. That is, the present invention provides the following [1] to
[28] .
[0020] [1] A release film comprising a resin layer (A) on one surface of a substrate film and a resin layer (B) on the other surface, wherein the resin layer (A) contains a silicone resin release agent and has a thickness of 0.2 to 2.0 μm, and the resin layer (B) contains a non-silicone resin release agent.
[0021] [2] A release film comprising a resin layer (A) on at least one side of a substrate film,
[0022] The aforementioned resin layer (A) is a cured product of a resin layer composition comprising a curable silicone resin and a light release agent, wherein the aforementioned light release agent has a dimethylsiloxane skeleton (DM) represented by the following formula (I) and a methylphenylsiloxane skeleton (MP) represented by the following formula (II), and the thickness of the resin layer (A) is 0.2 to 1.5 μm.
[0023]
[0024]
[0025] [3] The release film according to [2] above, wherein the maximum cross-sectional height (Rt) of the film surface opposite to the surface on which the resin layer (A) is provided is 2.0 μm or less.
[0026] [4] The release film according to [2] or [3] above, wherein the surface of the substrate film opposite to the surface provided with the resin layer (A) comprises a polyester layer, and the polyester layer contains 0.4 to 1.0% by mass of particles having an average particle size of 1 to 6 μm.
[0027] [5] The release film according to any one of [2] to [4] above, wherein the light release agent has a mass average molecular weight of 10,000 to 100,000.
[0028] [6] The release film according to any one of [1] to [5] above, wherein the elastic modulus of the resin layer (A) at 25° C. measured using a nanoindenter is 500 MPa or less.
[0029] [7] The release film according to [1] or [6], wherein the non-silicone resin-based release agent is at least one selected from the group consisting of wax, long-chain alkyl-containing compounds, and fluorine compounds.
[0030] [8] The release film according to [1], [6] or [7] above, wherein the content of the release agent in the non-volatile component of the resin layer (B) is 10 to 70% by mass.
[0031] [9] The release film according to any one of [1] and [6] to [8] above, wherein the resin layer (B) contains substantially no particles.
[0032]
[10] The release film according to any one of [1] to [9] above, wherein the normal peel strength of the resin layer (A) measured by the following evaluation method is 5 g / 25 mm or less.
[0033] Evaluation method:
[0034] After attaching Tesa acrylic adhesive tape "No. 7475" to the resin layer (A) of the release film, the film was cut into a size of 25 mm x 150 mm and left at room temperature for 1 hour. The film was peeled off at 180° at a tensile speed of 0.3 m / min and the peeling force was measured.
[0035]
[11] The release film according to any one of [1] and [6] to
[10] above, wherein a primer layer is provided between at least one of the resin layer (A) or the resin layer (B) and the substrate film.
[0036]
[12] The release film according to
[11] above, wherein the primer layer is an antistatic layer.
[0037]
[13] The release film according to
[11] or
[12] above, wherein the primer layer contains the following compounds (A) to (C).
[0038] (A) A polymer in which a compound containing thiophene or a thiophene derivative is doped with another anionic compound, or a polymer in which a compound containing thiophene or a thiophene derivative has an anionic group and is self-doped
[0039] (B) Polyhydroxy compounds
[0040] (C) one or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins
[0041]
[14] The release film according to any one of [1] and [6] to
[13] , wherein the surface resistivity of at least one surface of the resin layer (A) or the resin layer (B) is 1×10 12 Ω / □ or less.
[0042]
[15] The release film according to any one of [1] to
[14] above, wherein the base film is a polyester film.
[0043]
[16] The release film according to
[15] above, wherein the polyester film has a three-layer structure.
[0044]
[17] The release film according to any one of [1] to
[16] above, wherein the post-pressing re-peeling rate of the resin layer (A) evaluated by the following method is 100% or less.
[0045] Evaluation method:
[0046] An acrylic adhesive tape (Tesa "No. 7475") was attached to the resin layer (A) and cut into a size of 25 mm x 150 mm, and allowed to stand at room temperature for 1 hour. The tape was peeled off at 180° at a tensile speed of 0.3 m / min, and the peeling force was recorded as (F1).
[0047] Next, the laminate was laminated in contact with the resin layer (A) surface, and a pressing treatment was performed for 20 hours at a temperature of 40°C, a humidity of 90% RH, and a load of 1 MPa. An acrylic adhesive tape (Tesa's "No.7475") was attached to the treated resin layer (A) surface, cut into a size of 25 mm × 150 mm, and left at room temperature for 1 hour. The peeling was performed at 180° under a tensile speed of 0.3 m / min, and the peeling force was recorded as (F2).
[0048] The re-peeling rate after pressing was calculated according to the following formula.
[0049] Re-peeling rate after pressing (%) = (F2-F1) / F1×100
[0050]
[18] The release film according to any one of [1] to
[17] above, wherein the center line average roughness (Ra(A)) of the surface of the resin layer (A) is 30 nm or less.
[0051]
[19] The release film according to any one of [1] or [6] to
[18] above, wherein the center line average roughness (Ra(B)) of the surface of the resin layer (B) is 60 nm or less.
[0052]
[20] A pressure-sensitive adhesive sheet comprising the release film according to any one of [1] to
[19] above and another release film via a pressure-sensitive adhesive layer.
[0053]
[21] The pressure-sensitive adhesive sheet according to
[20] above, wherein the pressure-sensitive adhesive layer is formed from an acrylic pressure-sensitive adhesive composition.
[0054]
[22] The pressure-sensitive adhesive sheet according to
[20] or
[21] above, wherein the pressure-sensitive adhesive layer has an elastic modulus (25° C.) of 6.0 MPa or less.
[0055]
[23] The pressure-sensitive adhesive sheet according to any one of
[20] to
[22] above, wherein the pressure-sensitive adhesive layer comprises 2-ethylhexyl acrylate and / or butyl acrylate.
[0056]
[24] The pressure-sensitive adhesive sheet according to any one of
[20] to
[23] above, which is used as a transparent pressure-sensitive adhesive sheet for optical use.
[0057]
[25] The release film according to any one of [1] to
[19] above, which is used for a display.
[0058]
[26] The release film according to any one of [1] to
[19] above, which is used for a foldable display.
[0059]
[27] A method for using a pressure-sensitive adhesive sheet, comprising laminating the pressure-sensitive adhesive sheet according to any one of
[20] to
[23] above to an optical member on a surface of the pressure-sensitive adhesive layer exposed after peeling off the other release film.
[0060]
[28] The method for using the pressure-sensitive adhesive sheet according to
[27] above, wherein the optical component is a polarizing plate or a touch sensor.
[0061] Effects of the Invention
[0062] According to the release film of the present invention, it is possible to provide a release film and a film laminate that achieve ultra-light releasability against various adhesives and in which the release characteristics of the release layer are not easily changed by blocking. DETAILED DESCRIPTION
[0063] Hereinafter, an example of an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment described below, and can be implemented with arbitrary modifications within the scope of the gist of the present invention.
[0064] <<<Release film>>>
[0065] A release film according to an example of an embodiment of the present invention (hereinafter, sometimes referred to as "the present release film") is a release film having a resin layer (A) on one surface of a base film and a resin layer (B) on the other surface. The release film is a roll-shaped release film (release film roll) that is wound up, and can also be stored in the form of a release film roll. In this case, the release layer (A) can be arranged on either the inner side or the outer side of the roll.
[0066] The release film is characterized in that the resin layer (A) on one surface contains a silicone resin release agent. The thickness of the resin layer (A) is 0.2 to 2.0 μm, and the elastic modulus of the resin layer (A) at 25° C. measured by a nanoindenter is preferably 500 MPa or less. In addition, the resin layer (B) on the other film surface is characterized in that it contains a non-silicone resin release agent.
[0067] When the release film having the above structure is rolled, the surface of the resin layer (A) overlaps the surface of the resin layer (B). In this case, the damage caused by the close contact of the resin layer (B) to the surface of the resin layer (A) can be reduced, and adhesion can be suppressed, and the heavy peeling of the resin layer (A) at the lower roll portion of the roll, which further applies pressure to the film, and the deterioration of the surface appearance can be prevented. In addition, the resin layer (A) achieves ultra-light peelability, but because it does not contain particles in essence, the adhesion to the base film is also good, and there is no particle shedding, so the migration to the adhesive tape can also be reduced.
[0068] <<Base film>>
[0069] The substrate film in the present release film is not particularly limited in material as long as it is in the form of a film. For example, it can be made of paper, resin, metal, etc. Among these, resin is preferred from the viewpoint of mechanical strength and flexibility.
[0070] As the resin substrate film, for example, a film formed into a film by polymers such as polyethylene, polypropylene, polyester, polystyrene, polycarbonate, polyethersulfone, polyamide, polyimide, etc. can be cited. In addition, as long as it can be made into a film, it can also be a mixture of these materials (polymer blend) or a composite of structural units (copolymer).
[0071] Among the films exemplified above, polyester films are particularly preferred because they are excellent in physical properties such as heat resistance, flatness, optical characteristics, and strength.
[0072] <Polyester film>
[0073] The polyester film constituting the laminated film of the present invention may be a single-layer structure or a multi-layer structure. In addition to the 2-layer and 3-layer structures, it may also be a 4-layer or more multi-layer structure as long as it does not exceed the gist of the present invention, without particular limitation. In the present invention, the polyester film formed by at least 3 layers is preferred. In addition, as the polyester film, a biaxially stretched polyester film is preferred from the aspects of filmization and dimensional stability.
[0074] The polyester used in the present invention may be a homopolyester or a copolyester. In the case of being formed by a homopolyester, it is preferably obtained by polycondensing an aromatic dicarboxylic acid with an aliphatic diol. As aromatic dicarboxylic acids, terephthalic acid, 2,6-naphthalene dicarboxylic acid, etc. can be cited, and as aliphatic diols, ethylene glycol, diethylene glycol, 1,4-cyclohexanedimethanol, etc. can be cited. As representative polyester examples, polyethylene terephthalate, etc. On the other hand, as the dicarboxylic acid component of the copolyester, one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, adipic acid, sebacic acid, hydroxycarboxylic acid (such as p-hydroxybenzoic acid esters, etc.) can be cited, and as the diol component, one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, neopentyl glycol, etc. can be cited.
[0075] In the case of forming a copolyester, one obtained by polycondensing a dicarboxylic acid component and a diol component can be cited. As the dicarboxylic acid component, one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, adipic acid, sebacic acid, hydroxycarboxylic acid (such as p-hydroxybenzoic acid esters, etc.) can be cited, and as the diol component, one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, neopentyl glycol, etc. can be cited. The copolyester preferably contains a copolymer of the third component of 30 mol% or less relative to the total of the dicarboxylic acid component and the diol component.
[0076] The main component resin refers to the resin having the largest mass proportion among the resins constituting the polyester film, and may account for 50 mass % or more, 75 mass % or more, 90 mass % or more, or 100 mass % of the resins constituting the polyester film.
[0077] As the polymerization catalyst of the polyester film, there is no particular limitation, and conventionally known compounds can be used, for example, antimony compounds, titanium compounds, germanium compounds, manganese compounds, aluminum compounds, magnesium compounds, calcium compounds, etc. can be cited. Among them, titanium compounds and germanium compounds are preferred because of their high catalytic activity, ability to polymerize in small amounts, small amounts of metal remaining in the film, and increased brightness of the film. In addition, germanium compounds are expensive, and therefore, titanium compounds are further preferred.
[0078] In the case of polyester using a titanium compound, the titanium content is preferably 50 ppm or less, more preferably 1 to 20 ppm, and even more preferably 2 to 10 ppm. If the content of the titanium compound is too high, the polyester may be deteriorated during the process of melt extrusion, and may become a film with a strong yellow tone. On the other hand, if the content is too low, the polymerization efficiency may be poor, the cost may increase, and a film with sufficient strength may not be obtained.
[0079] In addition, when using polyester based on titanium compounds, it is preferred to use a phosphorus compound to reduce the activity of the titanium compound for the purpose of suppressing degradation in the process of melt extrusion. As the phosphorus compound, orthophosphoric acid is preferred if the productivity and thermal stability of the polyester are taken into consideration. The phosphorus content is preferably in the range of 1 to 300 mass ppm, more preferably 3 to 200 mass ppm, and further preferably 5 to 100 mass ppm relative to the amount of melt-extruded polyester. If the content of the phosphorus compound is below the above upper limit, it will not cause gelation or foreign matter. In addition, if it is above the above lower limit, the activity of the titanium compound can be sufficiently reduced, coloring can be suppressed, and a film with a yellow tint will not be formed.
[0080] In order to suppress the precipitation amount of oligomer components, a film can be manufactured using polyester having a small content of oligomer components as a raw material. As a method for manufacturing polyester having a small content of oligomer components, various known methods can be used, for example, a method of carrying out solid phase polymerization after manufacturing polyester can be cited.
[0081] In addition, the amount of oligomer components precipitated can be suppressed by making the polyester film have a structure of three or more layers and making the outermost layer of the polyester film a layer using a polyester raw material with a small content of oligomer components. In addition, the polyester can be obtained by performing an esterification or transesterification reaction, then raising the reaction temperature, and performing melt polycondensation under reduced pressure.
[0082] The polyester film may contain an ultraviolet absorber to improve the weather resistance of the film and prevent degradation of adherends (such as liquid crystals), etc. The ultraviolet absorber is not particularly limited as long as it is a compound that absorbs ultraviolet rays and can withstand the heat applied in the polyester film production process.
[0083] As the ultraviolet absorber, there are organic ultraviolet absorbers and inorganic ultraviolet absorbers, but from the viewpoint of transparency, organic ultraviolet absorbers are preferred. As the organic ultraviolet absorber, there is no particular limitation, and for example, cyclic imino ester, benzotriazole, benzophenone, etc. can be cited. From the viewpoint of durability, cyclic imino ester and benzotriazole are more preferred. In addition, two or more ultraviolet absorbers can also be used in combination.
[0084] In order to impart slipperiness and prevent scratches in each process as the main purpose, particles can also be mixed in the polyester layer of the polyester film. In the case of mixing particles, the type of particles to be mixed is not particularly limited as long as they can impart slipperiness. As specific examples, for example, inorganic particles such as silicon dioxide, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, zirconium oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin can be cited. Furthermore, it is also possible to use particles formed by precipitating and microdispersing a part of metal compounds such as catalysts in the polyester manufacturing process. Among these, silicon dioxide particles and calcium carbonate particles are particularly preferred in terms of being easy to produce effects in a small amount.
[0085] The average particle size of the particles is preferably in the range of 0.01 to 5 μm, more preferably 0.03 to 4 μm, and further preferably 0.05 to 3.0 μm. When the average particle size is at most the upper limit, the haze of the film is suppressed to a low level, and the film has good slip properties.
[0086] Furthermore, the particle content in the polyester layer of the polyester film is preferably 5% by mass or less, more preferably in the range of 0.001 to 3% by mass, further preferably 0.01 to 1% by mass, and particularly preferably 0.05 to 0.5% by mass. In the absence of particles or in the case of a small amount, the transparency of the film becomes high, and a good film is obtained. However, in order to prevent the slip property from being reduced, it is sometimes necessary to add particles to the coating layer to improve the slip property. In addition, if the particle content is below the above upper limit, the haze does not increase, and sufficient transparency of the film can be ensured.
[0087] The shape of the particles used should not be particularly limited, and spherical, blocky, rod-shaped, flat, etc. can be used, and there are no particular restrictions on their hardness, specific gravity, color, etc. These series of particles can be used in combination of two or more as needed.
[0088] The method of adding particles to the polyester layer is not particularly limited, and a conventionally known method can be used. For example, the particles can be added at any stage of manufacturing the polyester constituting each layer, but preferably added after the esterification or transesterification reaction is completed.
[0089] The polyester film may be formed into a multilayer structure of two or more layers, but a polyester film of a three-layer structure is preferred. If a three-layer structure is formed, as described later, the polyester layers (surface layers) on both surfaces may contain particles, and the middle layer may not contain particles. Therefore, the slip property, anti-blocking property, etc. are improved, and the transparency of the polyester film may also be improved. It should be noted that the polyester constituting each layer is as described above.
[0090] In addition, when the polyester film is a multilayer structure of two or more layers, the average particle size of the particles used in the polyester layer on the side opposite to the side where the release layer is provided (the anti-release surface) (typically, the polyester layer on the side where the release layer is not provided) is preferably in the range of 1 to 6 μm, more preferably 2 to 5 μm, and particularly preferably 3 to 5 μm. In addition, the content of the particles in the polyester layer is, for example, 0.03 to 1.0 mass%, preferably 0.3 to 1.0 mass%, more preferably 0.4 to 1.0 mass%, and particularly preferably 0.4 to 0.8 mass%. By satisfying the above-mentioned average particle size and addition amount at the same time, the maximum cross-sectional height (Rt) of the anti-release surface becomes large, and the release film has a moderate concavo-convex shape, and both anti-blocking properties and release properties can be achieved.
[0091] When the polyester film is composed of a single layer, the single polyester layer preferably also contains particles from the viewpoint of anti-blocking and mold release properties, and the average particle size and the amount of particles added are preferably within the above ranges.
[0092] In a polyester film having two or more layers, the polyester layer (surface layer) on the side where the release layer is provided may or may not contain particles, but preferably contains particles from the viewpoint of slip properties, etc. It is preferred that the particle content (mass %) in the polyester layer (surface layer) on the side where the release layer is provided is less than the particle content (mass %) in the polyester layer on the side opposite to the side where the release layer is provided (anti-release surface). Specifically, the particle content (mass %) in the polyester layer on the side where the release layer is provided is preferably in the range of 0.001 to 0.8 mass %, more preferably 0.01 to 0.5 mass %, and further preferably 0.02 to 0.2 mass %.
[0093] It should be noted that, in addition to the above-mentioned particles, conventionally known ultraviolet absorbers, antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc. may be added to the polyester film of the present invention as required.
[0094] The thickness of the polyester film in the present invention is not particularly limited as long as it is within a range that allows film formation as a film, but is preferably 10 to 300 μm, more preferably 15 to 200 μm, further preferably 25 to 125 μm, and most preferably 38 to 75 μm.
[0095] <Method for producing polyester film>
[0096] Next, the manufacturing example of the polyester film is specifically described, but it is not limited to any of the following manufacturing examples. For example, in the case of manufacturing a biaxially stretched polyester film, the following method can be cited: First, the polyester raw material described above is melt-extruded from the die head using an extruder, and the molten sheet is cooled and solidified using a cooling roller to obtain an unstretched sheet. In this case, in order to improve the flatness of the sheet, it is preferred to improve the adhesion between the sheet and the rotating cooling drum, and preferably an electrostatic application densification method or a liquid coating densification method is used. Next, the obtained unstretched sheet is stretched in a single direction using a roller or tenter-type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Then, it is stretched in a direction orthogonal to the stretching direction of the first stage, usually at 70 to 170°C, with a stretching ratio of usually 2.5 to 7 times, preferably 3.0 to 6 times. Then, heat treatment is performed at a temperature of 180 to 270°C under tension or under relaxation of less than 30% to obtain a biaxially oriented film. In the above stretching, a method of performing unidirectional stretching in two or more stages may also be adopted. In this case, it is preferably performed in such a way that the final stretching ratios in the two directions are within the above ranges.
[0097] In addition, regarding the manufacture of polyester film, a simultaneous biaxial stretching method can also be used. The simultaneous biaxial stretching method is a method of simultaneously stretching and orienting the aforementioned unstretched sheet in the mechanical direction and the width direction in a state of temperature control of usually 70 to 120°C, preferably 80 to 110°C. As a stretching ratio, it is usually 4 to 50 times, preferably 7 to 35 times, and more preferably 10 to 25 times in terms of area ratio. And then, heat treatment is carried out at a temperature of 170 to 270°C, under tension or under relaxation of less than 30%, to obtain a stretched oriented film. Regarding the simultaneous biaxial stretching device using the above-mentioned stretching method, a previously known stretching method such as a screw method, a pantograph method, a linear drive method, etc. can be used.
[0098] <<Resin layer (A)>>
[0099] Next, the formation of the resin layer (A) constituting the release film in the present invention will be described.
[0100] The resin layer (A) is a layer formed by curing a resin layer (A) composition having a curable silicone resin as a main component resin, and is disposed on at least one side of the substrate film. The resin layer (A) layer can also be said to be a release layer containing a cured product formed by curing the resin layer (A) composition.
[0101] It should be noted that the above-mentioned "main component resin" refers to the resin with the largest mass proportion in the resins constituting the present resin layer (A) composition, and it is assumed that it accounts for more than 50 mass%, or more than 75 mass%, or more than 90 mass%, or 100 mass% of the resins constituting the present resin layer (A) composition.
[0102] The resin layer (A) in the present invention preferably contains a curable silicone resin.
[0103] As the curable silicone resin, a resin containing a curable silicone resin as a main component may be used, or a modified silicone produced by graft polymerization with an organic resin such as an acrylic resin, a polyurethane resin, an epoxy resin, an alkyd resin, etc. In addition, when the adhesive layer is a silicone adhesive, it is preferably composed of a fluorinated silicone resin.
[0104] As the type of curable silicone resin, any existing curing reaction type such as a heat curing type such as an addition type / condensation type, an electron beam curing type such as an ultraviolet curing type, etc. can be used, and multiple curable silicone resins can also be used in combination. Furthermore, there is no particular limitation on the coating form of the curable silicone resin when forming the resin layer (A), and it can be a form dissolved in an organic solvent, a solvent-free form, or a water-based emulsion form.
[0105] Solvent-free curable silicone is a silicone with a viscosity that allows coating even without dilution with a solvent. It is a silicone resin with a relatively low molecular weight and is composed of short polysiloxane chains.
[0106] On the other hand, solvent-based curable silicone refers to a silicone resin whose viscosity is so high that it cannot be applied unless diluted with a solvent, and is a silicone having a higher molecular weight than solvent-free curable silicone.
[0107] Solvent-based curable silicone is preferred from the viewpoints of good adhesion to the substrate film, uniform coating appearance without coating unevenness, and easy adjustment of the thickness of the resin layer (A).
[0108] The type of silicone resin used in the present invention is not limited. From the viewpoint of excellent mold release properties such as light peelability, a curable silicone resin containing an alkenyl group is preferably used in the present invention. Among the curable silicone resins containing an alkenyl group, those represented by the following general formula (1) can be exemplified as diorganopolysiloxanes.
[0109] R (3-a) X a SiO-(RXSiO) m -(R2SiO) n -SiX a R (3-a)···(1)
[0110] In the general formula (1), R is a monovalent hydrocarbon group having 1 to 10 carbon atoms, and X is an organic group containing an alkenyl group. a is an integer of 0 to 3, preferably 1, m is 0 or more, and when a=0, m is 2 or more, and m and n are numbers satisfying 100≤m+n≤20000, respectively. In addition, the above formula should not refer to a block copolymer. R is a monovalent hydrocarbon group having 1 to 10 carbon atoms, and specifically, alkyl groups such as methyl, ethyl, propyl, and butyl, cycloalkyl groups such as cyclohexyl, phenyl, and aryl groups such as tolyl can be mentioned, and methyl and phenyl are particularly preferred. X is an organic group containing an alkenyl group, preferably one having 2 to 10 carbon atoms, and specifically, vinyl, allyl, hexenyl, octenyl, acryloyl propyl, acryloyl methyl, methacryloyl propyl, cyclohexenyl ethyl, vinyloxy propyl, and the like can be mentioned, and vinyl, hexenyl, and the like are particularly preferred. Specific examples include dimethylsiloxane·methylhexenylsiloxane copolymers (96 mol % of dimethylsiloxane units and 4 mol % of methylhexenylsiloxane units) terminated with trimethylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methylhexenylsiloxane copolymers (97 mol % of dimethylsiloxane units and 3 mol % of methylhexenylsiloxane units) terminated with dimethylvinylsiloxy groups at both ends of the molecular chain, and dimethylsiloxane·methylhexenylsiloxane copolymers (95 mol % of dimethylsiloxane units and 5 mol % of methylhexenylsiloxane units) terminated with dimethylhexenylsiloxy groups at both ends of the molecular chain.
[0111] Next, as the polyorganosiloxane containing SiH groups required to react with the curable silicone resin containing alkenyl groups to form a stronger silicone release layer, an organohydrogenpolysiloxane having at least 2, preferably 3 or more hydrogen atoms bonded to silicon atoms in one molecule, and a linear, branched, or cyclic organohydrogenpolysiloxane can be used, and the compounds represented by the following general formula (2) can be mentioned, but are not limited to these.
[0112] HkDJ 1 (3-b) SiO-(HR 1 SiO) x -(R 1 2SiO) y -SiR 1 (3-b) H b ···(2)
[0113] In the general formula (2), R 1It is a monovalent hydrocarbon group having 1 to 6 carbon atoms and not containing an aliphatic unsaturated bond. b is an integer of 0 to 3, and x and y are integers. Specific examples include methyl hydrogen polysiloxane terminated with trimethylsiloxy groups at both ends of the molecular chain, dimethylsiloxane·methyl hydrogen siloxane copolymer terminated with trimethylsiloxy groups at both ends of the molecular chain, methyl hydrogen polysiloxane terminated with dimethylhydrogen siloxy groups at both ends of the molecular chain, and dimethylsiloxane·methyl hydrogen siloxane copolymer terminated with dimethylhydrogen siloxy groups at both ends of the molecular chain.
[0114] Next, if specific examples of various types of commercially available silicone resins that can be used in the present invention are listed, KS-774, KS-775, KS-778, KS-779H, KS-847H, KS-856, X-62-2422, X-62-2461, X-62-1387, X-62-5039, X-62-5040, KNS-3051, X-62-1496, KNS320A, KNS316, X-62-1574A / B, X-62-7052, X-62-7028A / B, X-62-7619, X-62-7213, X-41-3035, Momentive Performance YSR-3022, TPR-6700, TPR-6720, TPR-6721, TPR6500, TPR6501, UV9300, UV9425, XS56-A2775, XS56-A2982, UV9430, TPR6600, TPR6604, TPR6605, DOW CORNING SRX357, SRX211, SD7220, SD7292, LTC750A, LTC760A, LTC303E, SP7259, BY24-468C, SP7248S, BY24-452, DKQ3-202, DKQ3-203, DKQ3-204, DKQ3-205, DKQ3-210 manufactured by TORAY CO., LTD., DEHESIVE series manufactured by Wacker Asahikasei Silicone Co., Ltd., DEHESIVE 636, 919, 920, 921, 924, 929, etc., but not limited to these.
[0115] The resin layer (A) preferably uses a platinum catalyst that promotes an addition reaction. Examples of this component include platinum compounds such as chloroplatinic acid, alcohol solutions of chloroplatinic acid, complexes of chloroplatinic acid and olefins, complexes of chloroplatinic acid and alkenylsiloxane, platinum black, platinum-loaded silica, and platinum-loaded activated carbon.
[0116] The content of the curing catalyst in the resin layer (A) is preferably 0.5 to 500 mass ppm, more preferably 5 mass ppm or more, and further preferably 10 mass ppm or more, relative to the curable silicone resin in terms of metal conversion, and more preferably 300 mass ppm or less, and further preferably 200 mass ppm or less. If the content of the platinum-based catalyst in the release layer is above the above lower limit, sufficient peeling force is obtained, the curing reaction proceeds sufficiently, and undesirable conditions such as deterioration of the coating surface are not generated. On the other hand, if the content of the platinum-based catalyst in the resin layer (A) is below the above upper limit, it is cost-effective, and the reactivity is improved, and undesirable conditions in the process such as the generation of gel foreign matter are not caused.
[0117] In addition, the reactivity of the addition reaction is very high, so depending on the situation, acetylene alcohol is sometimes added as a reaction inhibitor. This component is an organic compound having a carbon-carbon triple bond and a hydroxyl group, preferably a compound selected from the group consisting of 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol and phenylbutanol.
[0118] The content of the reaction control agent is preferably 0.001 to 5.0 parts by mass, more preferably 0.01 to 2.0 parts by mass, further preferably 0.05 to 1.5 parts by mass, and most preferably 0.1 to 0.5 parts by mass per 100 parts by mass of the total amount of the resin layer (A) composition (based on non-volatile components). By setting it within the above range, the easy peelability of the release film can be ensured without reducing the reaction activity, and the curing of the curable silicone resin is not hindered.
[0119] In the resin layer (A) constituting the release film, for the purpose of promoting hydrolysis / condensation reaction, a catalyst can be used in combination. As a specific example of the catalyst, acetic acid, butyric acid, maleic acid, citric acid and other organic acids, hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid and other inorganic acids, basic compounds such as triethylamine, tetrabutyl titanate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctoate, dibutyltin dioleate, diphenyltin diacetate, dibutyltin oxide, dibutyl dimethoxytin, dibutylbis (triethoxysilyl) tin, dibutyl benzyl maleate and other organic metal salts, KF, NH4F and other fluorine-containing compounds etc. can be enumerated. The above-mentioned catalyst can be used alone, or more than two kinds can be used in combination. Among them, in terms of the good aspect of the coating durability, organic metal salts are particularly preferred.
[0120] In order to adjust the peelability of the resin layer (A), various peel control agents may be used in combination. When the peeling force is increased, the content of the organopolysiloxane resin, silica particles, organosilicon materials with high peeling force, etc. is usually adjusted to be suitable for the resin layer (A) to obtain the desired peeling force.
[0121] Specific examples of commercially available heavy-duty release agents include KS-3800 and X-92-183 manufactured by Shin-Etsu Chemical Co., Ltd., and SD7292, BY24-843, and BY24-4980 manufactured by Dow Corning Toray Co., Ltd.
[0122] In the case of making the peeling force light, various low molecular weight siloxanes are selected and the content suitable for the resin layer (A) is adjusted so that the siloxane migration component can exert the demoulding performance. Examples of low molecular weight siloxane compounds include hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, etc. In addition, as other compounds of these low molecular weight cyclic siloxanes, there are: trimethylsiloxy end-capped dimethylsiloxane oligomers at both ends of the molecular chain; dimethylhydroxysiloxy end-capped dimethylsiloxane oligomers at both ends of the molecular chain, etc., and these compounds can also be mixed and used as needed.
[0123] As described above, the resin layer (A) composition may contain a light release agent as needed, preferably a silicone oil having a dimethylsiloxane skeleton (DM) represented by the following formula (3) and a methylphenylsiloxane skeleton (MP) represented by the following formula (4). The light release agent has a dimethylsiloxane skeleton (DM) and a methylphenylsiloxane skeleton (MP), so that even if it migrates to the adhesive layer to be bonded, it can penetrate into the interior of the adhesive layer, which can reduce the reduction in adhesive force. The ratio (DM:MP) of the dimethylsiloxane skeleton (DM) represented by the following formula (3) and the methylphenylsiloxane skeleton (MP) represented by the following formula (4) is preferably in the range of 98:2 to 70:30, more preferably in the range of 95:5 to 80:20, and particularly preferably in the range of 92:8 to 85:15, in terms of molar ratio. By making DM:PM within the above range, the releasability of the release film can be guaranteed.
[0124] The weight average molecular weight of the light release agent is preferably less than 10,000. When the weight average molecular weight of the light release agent is less than 10,000, it is advantageous in terms of migration and light release properties.
[0125]
[0126] These low molecular weight siloxane compounds are generally contained in the silicone resin as a migratory component in an amount of 0.1 to 15.0 mass %, preferably 0.5 to 10.0 mass %, and more preferably 0.5 to 5.0 mass %, so that the desired light release can be achieved. If it is 0.1 mass % or more, the migratory component is sufficient, so that the mold release property is fully exerted. If the content of the low molecular weight siloxane is 15.0 mass % or less, the migratory component does not precipitate excessively, and there is no worry about process contamination.
[0127] The resin layer (A) composition may contain a diluent solvent as required. Examples of the diluent solvent include aromatic hydrocarbons such as toluene, aliphatic hydrocarbons such as hexane, heptane, and isooctane, esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone (MEK) and isobutyl methyl ketone, alcohols such as ethanol and 2-propanol, and ethers such as diisopropyl ether and dibutyl ether. These are preferably used alone or in combination in consideration of solubility, coating properties, boiling point, and the like.
[0128] In addition, in the resin layer (A), it is preferred to use an organosilicon compound represented by the following general formula (5) in combination in order to improve the coating film adhesion with the thin film.
[0129] Si(X) d (Y) e (R 1 ) f ···(5)
[0130] [In the above formula, X is an organic group having at least one selected from the group consisting of an epoxy group, a mercapto group, a (meth)acryloyl group, an alkenyl group, a halogenated alkyl group and an amino group, and R 1 is a monovalent hydrocarbon group having 1 to 10 carbon atoms, Y is a hydrolyzable group, d is an integer of 1 or 2, e is an integer of 2 or 3, f is an integer of 0 or 1, d+e+f=4]
[0131] The organosilicon compound represented by the general formula (5) may be a compound having two hydrolyzable groups Y capable of forming a siloxane bond by a hydrolysis / condensation reaction (D unit source) or a compound having three hydrolyzable groups Y (T unit source).
[0132] In the general formula (5), the monovalent hydrocarbon group R 1 The carbon number of the group is 1 to 10, and a methyl group, an ethyl group, and a propyl group are particularly preferred.
[0133] In the general formula (5), the following groups can be exemplified as the hydrolyzable group Y. That is, methoxy, ethoxy, butoxy, isopropionyloxy, acetoxy, butyryloxy and amino groups. These hydrolyzable groups can be used alone or in combination. If a methoxy or ethoxy group is used, good storage stability can be imparted to the coating material. In addition, since it has appropriate hydrolyzability, it is particularly preferred.
[0134] Specific examples of the organic silicon compound contained in the resin layer (A) include vinyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-aminopropyl triethoxysilane, 5-hexenyl trimethoxysilane, p-phenylene trimethoxysilane, trifluoropropyl trimethoxysilane, γ-glycidoxypropyl triethoxysilane, and γ-glycidoxypropyl methyl diisopropionyloxysilane.
[0135] The resin layer (A) preferably contains substantially no particles. By substantially containing no particles in the resin layer (A), the peeling characteristics can be stabilized and the mobility can be reduced. It should be noted that substantially containing no particles means that the resin layer (A) may also contain particles as long as it is a small amount to the extent that does not hinder the effect of the present invention, for example, it may contain particles that are inevitably mixed in. The content of particles in the specific present resin layer (A) (A layer) is based on the non-volatile component, for example, less than 0.05% by mass, preferably less than 0.01% by mass, and more preferably less than 0.0001% by mass. It should be noted that the range of the content of particles in the present resin layer (A) composition based on the non-volatile component is also the same as the content of the above-mentioned particles.
[0136] Furthermore, within the scope not impairing the gist of the present invention, the resin layer (A) composition may contain a defoaming agent, a coating improver, a thickener, an organic lubricant, an antistatic agent, a conductive agent, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc. as needed.
[0137] The number average molecular weight (Mn) of the curable silicone resin is preferably 9000 or more and 350000 or less. If the number average molecular weight (Mn) of the curable silicone resin is above the above lower limit, when the adhesive layer is laminated on the release film, the amount of low molecular weight silicone resin dissolved or migrated to the adhesive layer can be reduced. In addition, by thick coating of the resin layer (A), it becomes easy to obtain a light peeling effect. On the other hand, if the number average molecular weight (Mn) of the curable silicone resin is below the above upper limit, the viscosity is prevented from becoming high and the fluidity of the resin layer (A) composition is reduced. Therefore, when the resin layer (A) composition is applied, it is prevented from producing striped uneven coating, and it becomes easy to make the surface of the resin layer (A) smooth.
[0138] From the above viewpoints, the number average molecular weight (Mn) of the curable silicone resin is preferably 9,000 or more, more preferably 10,000 or more, further preferably 20,000 or more, and particularly preferably 30,000 or more. On the other hand, it is preferably 350,000 or less, more preferably 50,000 or less, and further preferably 40,000 or less.
[0139] From the same viewpoint as the number average molecular weight, the mass average molecular weight (Mw) of the curable silicone resin is preferably 10,000 to 500,000, more preferably 20,000 or more, further preferably 50,000 or more, particularly preferably 80,000 or more, and more preferably 250,000 or less, further preferably 100,000 or less.
[0140] The ratio (Mw / Mn) of the mass average molecular weight (Mw) to the number average molecular weight (Mn) of the curable silicone resin is preferably 1.7 to 3.5, more preferably 1.9 to 3.0, and even more preferably 2.0 to 3.0. By satisfying this range, it is expected that the crosslinking reaction will proceed efficiently.
[0141] It should be noted that the number average molecular weight (Mn) and the mass average molecular weight (Mw) are values obtained by measuring polystyrene benchmarks according to gel permeation chromatography (GPC), and the specific measuring method is as follows: using a GPC measuring device, a chromatogram is measured, and based on a standard curve using standard polystyrene, the number average molecular weight (Mn) and the mass average molecular weight (Mw) are obtained. Specifically, 4 mg of the sample used for measurement is dissolved in 4 mL of THF as a measuring solution, and 100 μL of the measuring solution is injected into a GPC measuring device for measurement. Tetrahydrofuran (THF) is used as an eluent. "Ecosec8320" made by Tosoh Corporation is used in the analysis, and "TSKgel guardcolumn HXL-L" made by Tosoh Corporation is used as a guard column. For a column, 4 "TSKgelGMHXL" made by Tosoh Corporation are connected and used. In addition, the temperature of the column oven is 40 ° C, and the THF flow rate is 1.0 mL / min. The conditions are analyzed, and RI is used in the detection.
[0142] The curable silicone resin can be formed by a combination of two or more curable silicone resins. In this case, the average of the number average molecular weight (Mn) and the mass average molecular weight (Mw) of the two or more curable silicone resins is preferably within the above range. It should be noted that the so-called average here refers to the weighted average obtained by weighting the mass of each resin. In addition, when a main agent and a silicone crosslinking agent are used as the curable silicone resin, the mass average molecular weight (Mn), number average molecular weight (Mw), and Mw / Mn of the main agent can be within the above range.
[0143] The viscosity of the curable silicone resin at 25° C. when diluted with an n-heptane solvent to 15% by mass is preferably 1 to 400 mcps, more preferably 5 to 300 mcps, and even more preferably 10 to 200 mcps.
[0144] If the viscosity of the curable silicone resin is 1 mcps or more, the rebound can be suppressed by utilizing the appropriate viscosity of the coating liquid, thereby obtaining a uniform coating appearance with high visibility. Therefore, it is preferred that the viscosity is 400 mcps or less, because the fluidity of the resin layer (A) composition can be maintained, the generation of streak-like coating unevenness when coating the resin layer (A) composition can be suppressed, and the surface of the resin layer (A) can be made smooth.
[0145] The viscosity was measured by diluting a curable silicone resin with an n-heptane solvent to 15% by mass, and measuring the viscosity of the solution at 25° C. using an E-type viscometer (“TVE-22L” manufactured by Toki Sangyo Co., Ltd.).
[0146] For the curable silicone resin, when the silicone resin has alkenyl groups, the content of the alkenyl groups is preferably 0.4 to 2.5 mol%, more preferably 0.5 to 2.0 mol%, and even more preferably 0.5 to 1.5 mol% relative to the total amount of siloxane components. By satisfying this range, a constant amount or more of alkenyl groups is contained, so that the release layer is sufficiently cured, and on the other hand, the amount of alkenyl groups is not excessive, so that the release force after exposure to air can be prevented from becoming large.
[0147] For the curable silicone resin, when the silicone resin has Si-H groups, the content of the Si-H groups is preferably 0.8 to 2.5 mol%, more preferably 0.8 to 2.0 mol%, and further preferably 1.0 to 2.0 mol% relative to the total amount of the siloxane component. By satisfying this range, a constant amount or more of Si-H groups are contained, so that the release layer is sufficiently cured, and on the other hand, the amount of Si-H groups does not become excessive, thereby preventing the reaction with the adhesive layer and suppressing the re-peeling of the release film.
[0148] The curable silicone resin may contain alkenyl groups and Si-H groups (also referred to as "H groups") in the side chains and / or terminals of the main chain formed by siloxane bonds in the same structure. In this case, the content of alkenyl groups and Si-H groups is preferably within the above range.
[0149] The content of all silicone components in the release layer composition can be expressed as 1 H-NMR is measured by the integrated ratio of the dimethylsiloxane unit in the main chain to the other units. In addition, the content of vinyl and Si-H groups is expressed as the ratio to the total amount of functional groups bonded to the siloxane chain, and is measured by 1 However, the method is not limited to these methods.
[0150] From the viewpoint of ultra-light peeling, anti-adhesion, and increased inhibition of mobility, the thickness of the resin layer (A) is preferably 0.2 to 2.0 μm, more preferably 0.4 to 1.5 μm, further preferably 0.4 to 1.2 μm, and most preferably 0.4 to 1.0 μm. If the thickness of the resin layer (A) becomes less than 0.2 μm, as described later, even if the elastic modulus of the resin layer (A) is within a specified range, it is difficult to peel the resin layer (A) lightly. In addition, if it is thicker than 2.0 μm, it sometimes causes an increase in the mobility of the resin layer (A) component to migrate to an adhesive tape, etc., or sometimes it is not possible to fully prevent adhesion.
[0151] The elastic modulus of the resin layer (A) at 25°C is preferably 500 MPa or less, more preferably 65 to 400 MPa, and further preferably 80 to 300 MPa. By satisfying these ranges, good peelability can be shown for the adhesive layer. It should be noted that the elastic modulus of the resin layer (A) can be adjusted according to the type of silicone resin to be used, the thickness of the resin layer (A), etc. For example, if the resin layer (A) is thinned, there is a tendency for the elastic modulus to become higher. In addition, the elastic modulus referred to herein is a value measured using a nanoindenter.
[0152] The normal peeling force of the resin layer (A) is preferably 5 g / 25 mm or less, more preferably 0.1 to 4 g / 25 mm, and further preferably 0.5 to 3 g / 25 mm. If the normal peeling force is 5 g / 25 mm or less, good peeling properties can be shown for the adhesive layer whose elastic modulus decreases as the optical component becomes larger and thinner. On the other hand, if the normal peeling force exceeds 5 g / 25 mm, it sometimes becomes difficult to peel off from the adhesive layer, and the adhesive layer is sometimes transferred to the release film side due to deformation and rupture of the adhesive layer.
[0153] The residual adhesion rate of the resin layer (A) is an indicator of the mobility of the migrating components originating from the resin layer (A) to the adhesive tape to be attached. In a resin layer (A) with high mobility, a large amount of migrating components adhere to the overlapping evaluation film, so the peeling force of the adhesive tape attached to the evaluation film becomes smaller and the residual adhesion rate (%) also decreases. Therefore, it is better to have a high residual adhesion rate (%), preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. As long as the residual adhesion rate is 80% or more, it can be considered that there is no problem in actual use.
[0154] The re-peeling rate of the resin layer (A) after pressing is preferably 100% or less, more preferably 50% or less, and further preferably 20% or less. If the re-peeling rate after pressing is 100% or less, when the release film is rolled up, the re-peeling of the resin layer (A) at the lower roll portion of the roll to which pressure is applied by the film is suppressed to a small level, and the inconvenience caused by re-peeling does not occur. The method for estimating the re-peeling rate after pressing is described in the Examples.
[0155] The resin layer (A) can be formed by in-line coating in which the film surface is treated during the film forming step, or by off-line coating in which the film is coated on a temporarily manufactured film outside the system. Off-line coating is more preferred.
[0156] As a method for providing the resin layer (A) on the film, conventionally known coating methods such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, and curtain coating can be used.
[0157] The film constituting the release film of the present invention may be subjected to a surface treatment such as a corona treatment or a plasma treatment in advance.
[0158] The curing conditions when forming the resin layer (A) should not be particularly limited. When the resin layer (A) is provided by off-line coating, heat treatment is usually performed with the goal of performing the heat treatment at 80°C or higher for 10 seconds or more, preferably at 100 to 200°C for 3 to 40 seconds, more preferably at 120 to 190°C for 3 to 40 seconds, and further preferably at 150 to 180°C for 3 to 40 seconds.
[0159] In addition, heat treatment and active energy ray irradiation such as ultraviolet irradiation may be used in combination as needed. It should be noted that as an energy source for curing based on active energy ray irradiation, a known device or energy source may be used. For example, as a light source, a FUSION (H) lamp, a metal halide lamp, a high-pressure mercury lamp (ozone generating type, ozone-free type), a UV-LED, etc. are exemplified.
[0160] The active energy ray irradiation is not particularly limited, but in the case of ultraviolet ray irradiation, the irradiation rate may be 10 to 3000 mJ / cm in terms of the cumulative light intensity. 2 , preferably 50 to 2000 mJ / cm 2 , more preferably 100 to 1000 mJ / cm 2 By converting the accumulated light amount of ultraviolet irradiation into the above range, the curing of the resin layer (A) is promoted. On the other hand, the resin layer (A) is not damaged by excessive irradiation, and the peeling force after irradiation can be prevented from becoming heavier.
[0161] The release film of the present invention preferably has a surface resistivity of 1×10 12 The lower the surface resistivity of the resin layer (A) or the resin layer (B), the better the antistatic property is, and the charging of the film during the process can be suppressed, thereby preventing the adhesion of foreign matter and the like.
[0162] The center line average roughness (Ra(A)) of the resin layer (A) is preferably 30 nm or less. The center line average roughness (Ra(A)) is preferably 30 nm or less, so that ultralight peeling becomes possible. (Ra(A)) is further preferably 25 nm or less, and in particular, 20 nm or less. On the other hand, the lower limit is preferably 5 nm or more for the sake of film operability.
[0163] <<Resin layer (B)>>
[0164] The resin layer (B) in the present invention will be described below.
[0165] The resin layer (B) constituting the release film in the present invention can be any resin layer (B) provided on the surface of the substrate film opposite to the surface provided with the resin layer (A) and containing a non-silicone release agent, and more preferably containing a non-silicone release agent and having antistatic properties.
[0166] The non-silicone release agent used in the resin layer (B) is not particularly limited as long as it is a release agent other than a silicone compound, and a conventionally known release agent can be used, for example, a long-chain alkyl-containing compound, a fluorine compound, wax, etc.
[0167] Among these, long-chain alkyl compounds and waxes are preferred because of their low contamination and excellent blocking reduction, and long-chain alkyl compounds are more preferred from the viewpoint of particularly reducing blocking. These release agents may be used alone or in combination of two or more.
[0168] An organosilicon compound refers to a compound having a siloxane bond in the molecule, and also includes compounds having various functional groups in the side chain and / or the terminal of the main chain formed by the siloxane bond. Examples thereof include ether groups, hydroxyl groups, amino groups, epoxy groups, carboxylic acid groups, halogen groups such as fluorine, perfluoroalkyl groups, hydrocarbon groups (alkyl groups, alkenyl groups, aryl groups, various aromatic groups, etc.). When the resin layer (B) contains an organosilicon compound, it adheres strongly to the resin layer (A), the surface of the resin layer (A) is deformed, and the peeling properties of the resin layer (A) are deteriorated. Therefore, it is difficult to use it in the present release film.
[0169] The compound containing a long-chain alkyl group refers to a compound having a straight-chain or branched alkyl group having a carbon number of usually 6 or more, preferably 8 or more, and more preferably 12 or more. As the alkyl group, for example, hexyl, octyl, decyl, lauryl, octadecyl, behenyl, etc. can be cited. The compound having an alkyl group can, for example, include various polymer compounds containing long-chain alkyl groups, amine compounds containing long-chain alkyl groups, ether compounds containing long-chain alkyl groups, quaternary ammonium salts containing long-chain alkyl groups, etc. If heat resistance and contamination are considered, a polymer compound is preferred. In addition, from the viewpoint of effectively obtaining demoulding properties, a polymer compound having a long-chain alkyl group in the side chain is more preferred.
[0170] The polymer compound having a long-chain alkyl group in the side chain can be obtained by reacting a polymer having a reactive group with a compound having an alkyl group that can react with the reactive group. As the above-mentioned reactive group, for example, a hydroxyl group, an amino group, a carboxyl group, an acid anhydride, etc. can be mentioned. As the compound having these reactive groups, for example, polyvinyl alcohol, polyethyleneimine, polyvinylamine, polyester resin containing a reactive group, poly (meth) acrylic resin containing a reactive group, etc. can be mentioned. Among these, polyvinyl alcohol is preferred if demoulding properties and ease of operation are considered.
[0171] Examples of the compound having an alkyl group that can react with the reactive group include isocyanates containing long-chain alkyl groups such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, and behenyl isocyanate, acyl chlorides containing long-chain alkyl groups such as hexyl chloride, octyl chloride, decyl chloride, lauryl chloride, octadecyl chloride, and behenyl chloride, amines containing long-chain alkyl groups, and alcohols containing long-chain alkyl groups. Among these, isocyanates containing long-chain alkyl groups are preferred, and octadecyl isocyanate is particularly preferred in view of mold release properties and ease of handling.
[0172] In addition, the polymer compound having a long-chain alkyl group in the side chain can also be obtained by polymerizing a long-chain alkyl (meth)acrylate or copolymerizing a long-chain alkyl (meth)acrylate with other vinyl-containing monomers. Examples of the long-chain alkyl (meth)acrylate include hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and behenyl (meth)acrylate.
[0173] Wax is a wax selected from natural wax, synthetic wax, and waxes obtained by blending them. Natural wax refers to plant wax, animal wax, mineral wax, and petroleum wax. As plant wax, candelilla wax, carnauba wax, rice bran wax, wood wax, jojoba oil, etc. can be mentioned. As animal wax, beeswax, lanolin, spermaceti, etc. can be mentioned. As mineral wax, montan wax, ozokerite, ceresin, etc. can be mentioned. As petroleum wax, paraffin, microcrystalline wax, vaseline, etc. can be mentioned. As synthetic wax, synthetic hydrocarbons, modified wax, hydrogenated wax, fatty acid, acid amide, amine, imide, ester, ketone, etc. can be mentioned. As synthetic hydrocarbons, for example, Fischer-Tropsch wax (also known as Sasol wax) and polyethylene wax can be cited. In addition, the following polymers belonging to low molecular weight polymers (specifically, polymers with a viscosity average molecular weight of 500 to 20,000) can also be cited, namely, polypropylene, ethylene-acrylic acid copolymers, polyethylene glycol, polypropylene glycol, blocks or grafted combinations of polyethylene glycol and polypropylene glycol, etc. As modified waxes, montan wax derivatives, paraffin derivatives, microcrystalline wax derivatives, etc. can be cited. The derivatives here refer to compounds obtained by any treatment of purification, oxidation, esterification, saponification, or a combination thereof. As hydrogenated waxes, hydrogenated castor oil and hydrogenated castor oil derivatives can be cited.
[0174] Among the above waxes, synthetic waxes are preferred from the viewpoint of stable properties, polyethylene waxes are more preferred, and oxidized polyethylene waxes are further preferred. The number average molecular weight (Mn) of the synthetic wax is preferably in the range of 500 to 30,000, more preferably 1,000 to 15,000, and further preferably 2,000 to 8,000 from the viewpoint of stability of properties such as blocking and handling properties.
[0175] Fluorine compounds refer to compounds containing fluorine atoms in the compound. In terms of coating appearance based on in-line coating, organic fluorine compounds are suitable, for example, compounds containing perfluoroalkyl groups, polymers of olefin compounds containing fluorine atoms, aromatic fluorine compounds such as fluorobenzene, etc. can be cited. From the viewpoint of mold release, compounds having perfluoroalkyl groups are preferred. Among the fluorine compounds, compounds containing long-chain alkyl compounds described later can also be used.
[0176] Compounds having a perfluoroalkyl group include, for example, perfluoroalkyl (meth)acrylate, perfluoroalkyl methyl (meth)acrylate, 2-perfluoroalkyl ethyl (meth)acrylate, 3-perfluoroalkyl propyl (meth)acrylate, 3-perfluoroalkyl-1-methylpropyl (meth)acrylate, 3-perfluoroalkyl-2-propylene (meth)acrylate, and other perfluoroalkyl-containing (meth)acrylates, polymers thereof, perfluoroalkyl methyl vinyl ether, 2-perfluoroalkyl ethyl vinyl ether, 3-perfluoropropyl vinyl ether, 3-perfluoroalkyl-1-methylpropyl vinyl ether, 3-perfluoroalkyl-2-propylene vinyl ether, and other perfluoroalkyl-containing vinyl ethers, polymers thereof, etc. If heat resistance and contamination are considered, polymers are preferred. The polymer may be only a single compound or a polymer of multiple compounds. In addition, from the viewpoint of demolding properties, the perfluoroalkyl group preferably has 3 to 11 carbon atoms. It may be a polymer with a compound that also contains a long-chain alkyl compound described later. From the viewpoint of adhesion to the substrate, a polymer with vinyl chloride is also preferred.
[0177] When forming the resin layer (B), from the viewpoint of preventing the attachment of foreign matter, etc., it is preferred to contain an antistatic agent, for example, a polymer formed by doping a compound containing thiophene or a thiophene derivative with other anionic compounds, a polymer formed by self-doping a compound containing thiophene or a thiophene derivative having an anionic group, or a polymer containing a monomer having an alkylsulfonic acid ion as a counter ion as a component, etc. Among them, from the viewpoint of obtaining excellent antistatic performance, it is more preferred to contain a compound containing thiophene or a thiophene derivative.
[0178] For compounds containing thiophene or thiophene derivatives, a polymer formed by doping the compound containing thiophene or thiophene derivatives with other anionic compounds, or a polymer self-doped with an anionic group in the compound containing thiophene or thiophene derivatives, for example, a compound of the following formula (6) or the following formula (7) is polymerized in the presence of a polyanion.
[0179]
[0180] In the above formula (6), R 1 and R 2 Each independently represents a hydrogen atom, or an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, or the like having 1 to 20 carbon atoms.
[0181]
[0182] In the above formula (7), n represents an integer of 1-4.
[0183] Examples of the polyanion used in the polymerization include poly(meth)acrylic acid, polymaleic acid, polystyrenesulfonic acid, polyvinylsulfonic acid, etc. As a method for producing the above-mentioned polymer, for example, the method disclosed in Japanese Patent Application Laid-Open No. 7-90060 can be used.
[0184] In the present invention, it is suitable to use a compound of the above formula (7) wherein n is 2 and polystyrene sulfonic acid is used as the polyanion.
[0185] When these polyanions are acidic, they may be partially or entirely neutralized. As the base used for neutralization, ammonia, organic amines, and alkali metal hydroxides are preferred.
[0186] As a specific example of a polymer containing a monomer having an alkylsulfonic acid ion as a counter ion as a component, for example, a polymer having a constituent element represented by the following formula (8) as a repeating unit can be cited. It can be a homopolymer or a copolymer thereof, and further, it can be copolymerized with other various components. From the viewpoint of improving antistatic properties, a homopolymer is preferred.
[0187]
[0188] Examples of the structure of the polymer include the following: 1 is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, R 2 is -O- or -NH-, R 3 is an alkylene group having 1 to 6 carbon atoms or other structure that can form the structure of formula (8), R 4 , R 5 , R 6 At least one of X is a hydrogen atom, the other substituent is an alkyl group having 1 to 3 carbon atoms, or a hydroxyalkyl group having 2 to 3 carbon atoms in the alkyl group, - An alkylsulfonate ion having an alkyl group having 1 to 4 carbon atoms.
[0189] When forming the resin layer (B), in order to make the coating appearance and antistatic performance good, it is preferred to contain a polyhydroxy compound. As the polyhydroxy compound, it is preferred to use one or more compounds selected from polyglycerol and polyglycerol alkylene oxide adducts or their derivatives. Polyglycerol refers to a compound represented by the following general formula (9).
[0190]
[0191] In the above formula (9), n is 2 or more. In the present invention, n in the formula is usually in the range of 2 to 20, preferably 3 to 15, and more preferably 3 to 12.
[0192] The alkylene oxide adduct of polyglycerol means a product having a structure in which alkylene oxide is addition-polymerized to the hydroxyl group of polyglycerol represented by the above general formula (9).
[0193] Here, the structure of the alkylene oxide added to each hydroxyl group of the polyglycerol skeleton may be different. In addition, the alkylene oxide or its derivative need not be added to all hydroxyl groups as long as it is added to at least one hydroxyl group in the molecule.
[0194] The preferred substance of the alkylene oxide added to the polyglycerol is ethylene oxide or propylene oxide. If the alkylene chain of the alkylene oxide is excessively long, the hydrophobicity becomes stronger, the dispersibility in the coating liquid deteriorates, and there is a tendency for the antistatic property and transparency of the resin layer (B) to deteriorate. Ethylene oxide is particularly preferred. In addition, the addition number is preferably in the range of 200 to 2000, more preferably in the range of 300 to 1000, and further preferably in the range of 400 to 900, based on the number average molecular weight (Mn) of the final compound.
[0195] The above-mentioned polyglycerol or alkylene oxide adduct of polyglycerol may be used alone or in combination of two or more.
[0196] When forming the resin layer (B), various conventionally known polymers may be used as binder components from the viewpoint of improving the coating appearance and transparency, and specific examples of the polymers include polyester resins, polyurethane resins, acrylic resins, polyvinyl alcohol, vinyl chloride vinyl acetate copolymers, etc. From the viewpoint of making the resin layer (B) more solid and reducing adhesion, polyester resins and polyurethane resins are preferably used.
[0197] For example, polyester resins include those formed of the following polyvalent carboxylic acids and polyvalent hydroxy compounds as main constituents. That is, as polyvalent carboxylic acids, terephthalic acid, isophthalic acid, phthalic acid, phthalic acid, 4,4'-diphenyl dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, 2-potassium sulfoterephthalate, 5-sodium sulfoisophthalate, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof can be used. As the polyvalent hydroxy compound, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, terephthalic acid, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerol, trimethylolpropane, sodium dimethylolethylsulfonate, potassium dimethylolpropionate, etc. can be used.
[0198] Polyester resin is a polycondensate of polycarboxylic acid and polyhydroxy compound. Polycarboxylic acid and polyhydroxy compound can be selected from the above compounds, and one or more of each can be synthesized by polycondensation reaction according to conventional methods. In addition, polyester resin can be formed into an aqueous dispersion, in which case, hydrophilic functional groups can be appropriately introduced into the polyester resin.
[0199] Polyurethane resin refers to a polymer compound having a carbamate bond in the molecule. Polyurethane resin is usually made by the reaction of a polyol and an isocyanate. As polyols, polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, and acrylic polyols can be cited. These compounds can be used alone or in combination. Polyurethane resin can be an aqueous dispersion, in which case, for example, a hydrophilic functional group can be suitably introduced into the polyol.
[0200] Polycarbonate polyols are obtained by dealcoholization reaction of polyols and carbonate compounds. Examples of polyols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 3,3-dihydroxymethylheptane. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, and ethylene carbonate. Examples of polycarbonate polyols obtained by the reaction of these compounds include poly(1,6-hexamethylene) carbonate and poly(3-methyl-1,5-pentamethylene) carbonate.
[0201] Examples of the polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their anhydrides and polyols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamine, lactonediol, etc.
[0202] Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0203] In order to improve the adhesion with various functional layers, polycarbonate polyols and polyester polyols are more preferably used among the above-mentioned polyols.
[0204] Examples of the polyisocyanate compound used to obtain the polyurethane resin include aromatic diisocyanates such as toluene diisocyanate, xylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and toluidine diisocyanate, aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylene diisocyanate, methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate, and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidene dicyclohexyl diisocyanate. These may be used alone or in combination of a plurality of types.
[0205] When synthesizing the polyurethane resin, a chain extender may be used. The chain extender is not particularly limited as long as it has two or more active groups that react with isocyanate groups. Generally, chain extenders having two hydroxyl groups or amino groups are mainly used.
[0206] Examples of the chain extender having two hydroxyl groups include diols such as aliphatic diols such as ethylene glycol, propylene glycol, and butanediol, aromatic diols such as xylene glycol and bishydroxyethoxybenzene, and ester diols such as neopentyl glycol hydroxypivalate. Examples of the chain extender having two amino groups include aromatic diamines such as toluenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propylenediamine, hexylenediamine, 2,2-dimethyl-1,3-propylenediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, isopropylidenecyclohexyl-4,4′-diamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.
[0207] The polyurethane resin in the present invention may be prepared using a solvent as a medium, preferably water as a medium. In order to disperse or dissolve the polyurethane resin in water, there are: a forced emulsification type using an emulsifier, a self-emulsification type or a water-soluble type in which a hydrophilic group is introduced into the polyurethane resin, etc. In particular, a self-emulsification type in which an ionic group is introduced into the structure of the polyurethane resin to form an ionomer is preferred because of its excellent storage stability of the liquid and the water resistance, transparency and adhesion of the obtained coating layer.
[0208] In addition, as the ionic groups to be introduced, various groups such as carboxyl, sulfonic acid, phosphoric acid, phosphonic acid, quaternary ammonium salts can be cited, and carboxyl is preferred. As a method for introducing carboxyl groups into polyurethane resins, various methods can be used in various stages of the polymerization reaction. For example, there are the following methods: when synthesizing prepolymers, a method of using a resin having a carboxyl group as a copolymerization component, a method of using a component having a carboxyl group as a component of a polyol, a polyisocyanate, a chain extender, etc. It is particularly preferred to use a carboxyl-containing diol to introduce a desired amount of carboxyl groups according to the amount of the component input. For example, dimethylol propionic acid, dimethylol butyric acid, bis-(2-hydroxyethyl) propionic acid, bis-(2-hydroxyethyl) butyric acid, etc. can be copolymerized with diols used in the polymerization of polyurethane resins. In addition, the carboxyl group is preferably in the form of a salt neutralized with ammonia, amines, alkali metals, inorganic bases, etc. Particularly preferred are ammonia, trimethylamine, and triethylamine. The polyurethane resin can use the carboxyl groups from which the neutralizer is removed in the drying process after coating as crosslinking reaction sites with other crosslinking agents. This improves the stability in the liquid state before coating and further improves the durability, solvent resistance, water resistance, anti-blocking properties, etc. of the obtained coating layer.
[0209] Acrylic resins are polymers formed from polymerizable monomers including acrylic and methacrylic monomers. They can be homopolymers or copolymers, and further can be copolymers with polymerizable monomers other than acrylic and methacrylic monomers. In addition, copolymers of these polymers and other polymers (such as polyesters, polyurethanes, etc.) are also included. For example, block copolymers and graft copolymers. That is, acrylic resins can be acrylic modified polyester resins and acrylic modified polyurethane resins. Furthermore, polymers obtained by polymerizing polymerizable monomers in polyester solutions or polyester dispersions are also included (as a mixture of polymers, depending on the situation). Similarly, polymers obtained by polymerizing polymerizable monomers in polyurethane solutions and polyurethane dispersions are also included (as a mixture of polymers, depending on the situation). Similarly, polymers obtained by polymerizing polymerizable monomers in other polymer solutions or dispersions are also included (as a mixture of polymers, depending on the situation), which are also recorded as acrylic modified polyester resins and acrylic modified polyurethane resins in this specification. It should be noted that the above-mentioned polyesters and polyurethanes used in acrylic resins can be appropriately selected and used from the polyesters as the above-mentioned binder components and those exemplified as polyurethanes.
[0210] In order to further improve the adhesion with the base film, the acrylic resin may contain a hydroxyl group or an amino group.
[0211] The polymerizable monomers are not particularly limited, and representative compounds include, for example, various carboxyl-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyfumarate, and monobutyl hydroxyitaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, various (meth)acrylates such as dodecyl acrylate; various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-hydroxymethyl acrylamide or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, vinyltoluene, various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various halogenated vinyls such as vinyl chloride and vinylidene chloride; various conjugated dienes such as butadiene.
[0212] In order to improve the strength of the resin layer (B), a cross-linking agent may also be used in combination. The cross-linking agent may use materials known in the past, such as oxazoline compounds, epoxy compounds, melamine compounds, isocyanate compounds, carbodiimide compounds, organosilicon compounds, etc. From the perspective of improving the strength of the resin layer (B), melamine compounds are more preferred. In addition, two or more cross-linking agents may also be used in combination.
[0213] The resin layer (B) in the release film may contain particles for the purpose of improving the slipperiness of the film, but more preferably contains substantially no particles. The resin layer (B) contains substantially no particles, thereby stabilizing the release properties and reducing the migration of the release component.
[0214] It should be noted that "substantially free of" means that the resin layer (B) may contain particles, for example, particles that are inevitably mixed in, as long as the amount is small enough not to hinder the effect of the present invention. The content of particles in the specific resin layer (B) is, for example, less than 0.05% by mass, preferably less than 0.01% by mass, and more preferably less than 0.0001% by mass, based on the non-volatile component. It should be noted that the range of the content of particles in the resin layer (B) based on the non-volatile component is also the same as the content of the above particles.
[0215] Furthermore, the resin layer (B) may contain a defoaming agent, a coating improver, a thickener, an organic lubricant, an antistatic agent, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc. as needed without damaging the gist of the present invention.
[0216] In the resin layer (B), the content of the release agent in the nonvolatile component is preferably 10 to 70 mass %. When the content of the release agent is at least 10 mass %, good anti-blocking performance will be obtained.
[0217] In the resin layer (B), when a long-chain alkyl-containing compound is used as a non-silicone release agent, the long-chain alkyl-containing compound is preferably in the range of 5 to 90% by mass, more preferably 10 to 70% by mass, further preferably 20 to 60% by mass, and most preferably 20 to 40% by mass as a proportion of the total non-volatile components in the resin layer (B) composition. If the proportion of the long-chain alkyl-containing compound is within the above range, good anti-blocking performance is obtained, and the change in the release characteristics of the release layer caused by blocking is reduced, thereby further significantly suppressing the re-peeling of the release layer at the lower roll portion of the roll where pressure is applied to the film.
[0218] In the resin layer (B), when wax is used as a non-silicone release agent, the wax is preferably in the range of 5 to 90% by mass, more preferably 10 to 80% by mass, and further preferably 25 to 70% by mass as a proportion of all non-volatile components in the resin layer (B). If the proportion of the wax is in the above range, good anti-adhesion performance is obtained, and the change in the peeling characteristics of the release layer caused by adhesion is reduced, thereby further greatly suppressing the re-peeling of the release layer at the lower roll part of the roll where pressure is applied to the film. In addition, when used in combination with a melamine compound, re-peeling sometimes progresses. Therefore, when using wax, it is necessary to pay attention to the combination with a cross-linking agent or the like. On the other hand, compounds containing long-chain alkyl groups do not have the following problems and can be said to be more preferred.
[0219] Preferred combinations include combinations of a long-chain alkyl group-containing compound and a melamine compound, a long-chain alkyl group-containing compound and an oxazoline compound, a long-chain alkyl group-containing compound, a melamine compound, and an oxazoline compound, and a wax, a melamine compound, and an oxazoline compound.
[0220] The factors (presumptions) why wax, as a non-silicone-based release agent, has a higher releasability ratio than a long-chain alkyl group-containing compound due to combination with a crosslinking agent are considered as follows.
[0221] Wax has the characteristic of being oil-repellent in addition to water-repellency, and therefore has poor compatibility with the combined melamine compound, and the melamine compound is more likely to shrink.
[0222] On the other hand, the re-peeling rate evaluation of the present invention is carried out by performing a pressing process in the presence of moisture at high temperature (40°C) and high humidity (90% RH). Therefore, it becomes easy to form aggregates on the surface of the resin layer (B) which is a combination of wax and melamine compound, thereby improving the adhesion with the silicone release layer on the opposite side, and it is speculated that the re-peeling rate becomes larger.
[0223] As described above, the invention of the present application is characterized in that the oil repellent effect, which has not been paid attention to in conventional non-silicone release agents, is selected as a release agent, and a release film having a resin layer (B) is constructed.
[0224] In the resin layer (B), when a compound containing thiophene or a thiophene derivative is used as an antistatic agent, the compound containing thiophene or a thiophene derivative is preferably in the range of 5 to 50% by mass, more preferably 5 to 40% by mass, and further preferably 5 to 30% by mass as a proportion of the total non-volatile components of the resin layer (B). If it is in the above range, good antistatic properties can be obtained.
[0225] In the resin layer (B), the polyhydroxy compound preferably accounts for 10 to 80% by mass, more preferably 20 to 70% by mass, and even more preferably 30 to 65% by mass of the total nonvolatile components of the resin layer (B). Within the above range, good antistatic properties can be obtained.
[0226] As a proportion of the total non-volatile components of the resin layer (B), the binder component is preferably in the range of 5 to 50% by mass, more preferably 5 to 40% by mass, and further preferably 5 to 30% by mass. If the proportion of the binder component is within the above range, the strength of the resin layer (B) becomes good and blocking can be reduced.
[0227] The crosslinking agent preferably accounts for 5 to 70% by mass, preferably 10 to 60% by mass, and more preferably 15 to 50% by mass of the total nonvolatile components of the resin layer (B). If the crosslinking agent ratio is within the above range, the strength of the resin layer (B) becomes good and blocking can be reduced.
[0228] <Characteristics of resin layer (B)>
[0229] The resin layer (B) in the present invention may have the following properties.
[0230] The surface roughness (Ra(B)) of the resin layer (B) in the present release film is preferably 20 nm or more, more preferably 25 to 60 nm, more preferably 30 to 55 nm, and further preferably 38 to 50 nm. If it is 20 nm or more, after the release layer is provided, it is not easy to cause blocking in the rolled state. On the other hand, if the surface roughness is 60 nm or less, when the present release film is wound into a roll, the release properties of the release layer are maintained and the unevenness of the film is not transferred to the release layer.
[0231] The thickness of the resin layer (B) is preferably 0.005 to 0.25 μm, more preferably 0.008 to 0.15 μm, and further preferably 0.01 to 0.10 μm. By making the thickness of the resin layer (B) less than 0.25 μm, it is possible to suppress the migration of the non-silicone release agent components in the resin layer (B) to the release layer when the release film is wound into a roll. If the thickness of the resin layer (B) is greater than 0.005 μm, good anti-blocking properties can be imparted. It should be noted that it can be inferred that there are unreacted products of various compounds, reacted compounds, or mixtures thereof in the resin layer (B).
[0232] The surface resistivity of the resin layer (B) is preferably 1×10 12 Ω / □ or less, more preferably 1×10 10 Ω / □ or less, more preferably 1×10 8 Ω / □ or less, most preferably 1×106 Ω / □ or less. The lower limit of the surface resistivity is not particularly limited, but is preferably 1×10 4 Ω / □ or more. The lower the surface resistivity of the resin layer (B), the better the antistatic property is, and the charging of the film during the process can be suppressed, and the adhesion of foreign matter can be prevented.
[0233] The normal peeling force of the resin layer (B) is preferably 400 to 2000 g / 25 mm, more preferably 400 to 1500 g / 25 mm, and further preferably 400 to 1000 g / 25 mm. By setting the normal peeling force of the resin layer (B) to 2000 g / 25 mm or less, good anti-blocking properties can be imparted, and the re-peeling of the resin layer (A) at the lower roll portion of the roll to which pressure is applied by the film when the release film is wound into a roll can be suppressed.
[0234] The surface free energy of the resin layer (B) is preferably 50 mN / m or less, more preferably 40 mN / m or less, and further preferably 30 mN / m or less. By setting the surface free energy of the resin layer to 50 mN / m or less, good anti-blocking properties can be imparted, and the re-peeling of the release layer (A) at the lower roll portion of the roll to which the film applies pressure when the release film is rolled into a roll can be suppressed. The details of the surface free energy are described in the examples.
[0235] The elastic modulus of the resin layer (B) at 25°C is preferably 500 MPa or more. The elastic modulus here is a value measured by a nanoindenter. If the elastic modulus is 500 MPa or more, the resin layer (A) will not be peeled off again at the lower roll portion of the roll to which pressure is applied by the film when the release film is rolled into a roll.
[0236] <Base coating>
[0237] The release film preferably has a primer layer between at least one of the resin layer (A) or the resin layer (B) and the substrate film. The primer layer may be provided between the resin layer (A) and the substrate film, or between the resin layer (B) and the substrate film, or may be provided in both.
[0238] The primer layer is used not only for the purpose of improving the adhesion between the film and the resin layer (A) or the resin layer (B), but also for the purpose of imparting various functions to the release film. As the primer layer, for example, the peeling electrification in the process of suppressing the peeling of the functional layer such as the adhesive layer provided on the resin layer (A), the antistatic property for preventing the attachment of foreign matter, the oligomer sealing property for sealing the oligomers precipitated from the polyester film when heat-treated at high temperature for a long time, etc. can be cited. In the present release film, the primer layer with antistatic property is preferred. It should be noted that the primer layer can be a single layer or a composition of more than two layers.
[0239] In the primer layer with antistatic properties, as an antistatic agent, for example, a polymer formed by doping other anionic compounds in the compound containing thiophene or a thiophene derivative, or a polymer formed by self-doping with an anionic group in the compound containing thiophene or a thiophene derivative, or a polymer containing a monomer with an alkyl sulfonate ion as a counter ion as a component can be used.
[0240] In addition, in the present release film, from the viewpoint of having good antistatic performance, it is more preferable to contain a primer layer containing a compound containing thiophene or a thiophene derivative.
[0241] When forming a primer layer having antistatic properties, it is preferred to use at least one compound selected from the group consisting of polyglycerol represented by the general formula (9) and alkylene oxide adducts of polyglycerol or derivatives thereof for the purpose of improving the antistatic properties.
[0242] The base coat with antistatic performance may contain a binder component. As a binder, various polymers known in the past, such as polyester resins, acrylic resins, polyurethane resins, polyvinyl alcohol resins, etc., may be used. From the viewpoint of improving the transparency and antistatic properties of the base coat, polyurethane resins are preferred.
[0243] In order to improve the strength of the primer layer, a cross-linking agent may also be used. The cross-linking agent may use materials known in the past, such as oxazoline compounds, epoxy compounds, melamine compounds, isocyanate compounds, carbodiimide compounds, organosilicon compounds, etc. From the perspective of improving the strength of the primer layer, melamine compounds are more preferred. Two or more cross-linking agents may also be used.
[0244] In the primer layer, when a compound containing thiophene or a thiophene derivative is used as an antistatic agent, the compound containing thiophene or a thiophene derivative is preferably in the range of 5 to 50 mass %, more preferably 5 to 40 mass %, and further preferably 5 to 30 mass % as a proportion of the total non-volatile components of the primer layer. If it is in the above range, good antistatic properties can be obtained.
[0245] In the primer layer, the proportion of one or more compounds selected from polyglycerol and alkylene oxide adducts of polyglycerol or their derivatives in the total non-volatile components of the primer layer is preferably in the range of 10 to 80% by mass, more preferably 20 to 70% by mass, and further preferably 30 to 65% by mass. If it is in the above range, good antistatic properties can be obtained.
[0246] As the ratio of the binder component to the total non-volatile components of the primer layer, the binder component is preferably in the range of 5 to 50 mass %, more preferably 5 to 40 mass %, and further preferably 5 to 30 mass %. If the ratio of the binder component is in the above range, the strength of the primer layer becomes good and the antistatic property can be improved.
[0247] The crosslinking agent preferably accounts for 5 to 70% by mass, preferably 10 to 60% by mass, and more preferably 15 to 50% by mass of the total nonvolatile components of the primer layer. When the crosslinking agent ratio is within the above range, the strength of the primer layer becomes good and blocking can be reduced.
[0248] The primer layer having oligomer sealing properties may be provided with a primer layer having oligomer sealing properties containing an organic compound containing one or more metal elements selected from aluminum, titanium, and zirconium.
[0249] The primer layer having oligomer sealing properties may be directly provided on the base film, or may be provided on the primer layer having antistatic properties.
[0250] It is to be noted that it is presumed that unreacted products of various compounds in the resin composition, reacted compounds, or a mixture thereof are present in the primer layer.
[0251] <Primer Coat Characteristics>
[0252] The thickness of the primer layer having antistatic properties is preferably 0.005 μm to 0.25 μm, more preferably 0.008 μm to 0.15 μm, and further preferably 0.01 μm to 0.10 μm. When the thickness of the primer layer is within the above range, good antistatic properties can be imparted.
[0253] The surface resistivity of the primer layer with antistatic properties is preferably 1×10 12 Ω / □ or less, more preferably 1×10 10 Ω / □ or less, more preferably 1×10 8 Ω / □ or less, most preferably 1×10 6 Ω / □ or less. The lower limit of the surface resistivity is not particularly limited, but is preferably 1×10 4 Ω / □ or more. The lower the surface resistivity of the resin layer (B), the better the antistatic property is, and the charging of the film during the process can be suppressed, and the adhesion of foreign matter can be prevented.
[0254] <Method for forming resin layer (B) and primer layer>
[0255] Next, the method for forming the resin layer (B) and the primer layer will be described.
[0256] The resin layer (B) and the primer layer are formed by applying a coating liquid on the film, or by online coating in the film production process, or by so-called offline coating, which is coating on a temporarily produced film outside the system. Online coating is more preferred.
[0257] In-line coating is a method of coating in the process of manufacturing polyester film, specifically, a method of coating in any stage from melt extrusion of polyester to stretching, heat setting and winding. Usually, coating is performed on any of the unstretched sheets obtained by melting and quenching, stretched uniaxially stretched films, biaxially stretched films before heat setting, and films before winding after heat setting.
[0258] It is not limited to the following, but for example, in the biaxial stretching in sequence, in particular, after being coated on a uniaxially stretched film stretched in the length direction (longitudinal direction), the method of stretching in the transverse direction is excellent. According to the above method, film-making and the formation of the resin layer (B) can be carried out simultaneously, so there is an advantage in manufacturing cost. In addition, in order to stretch after coating, the thickness of the resin layer (B) can also be changed according to the stretching ratio, and compared with the offline coating film, the film coating can be easier. In addition, by arranging the resin layer (B) on the film before stretching, the resin layer (B) can be stretched together with the polyester film, thereby, the resin layer (B) can be firmly adhered to the polyester film.
[0259] Furthermore, in the production of a biaxially stretched polyester film, the film is stretched while the film ends are fixed by a clamp or the like, so that the film can be constrained in the longitudinal and transverse directions, and in the heat setting process, a high temperature can be applied while maintaining the flatness without introducing wrinkles, etc. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, so that the curing of the resin layer (B) and the primer layer is further advanced compared to offline coating, and a stronger coating film can be obtained.
[0260] When the resin layer (B) is set by online coating, it is preferred to manufacture the substrate film as follows: the above series of compounds are set as an aqueous solution or a water dispersion, and the resin layer (B) composition adjusted to a solid content concentration (total non-volatile components) of about 0.1 to 50% by weight is coated on the polyester film.
[0261] As a method for coating the resin layer (B) composition or the primer composition on a film, for example, conventionally known coating methods such as air knife coating, blade coating, rod coating, rod coating, knife coating, press coating, impregnation coating, reverse roll coating, transfer roll coating, gravure coating, lick roller coating, cast coating, spray coating, curtain coating, calender coating, and extrusion coating can be used.
[0262] The drying and curing conditions when forming the resin layer (B) and the primer layer on the film should not be particularly limited. When the resin layer (B) is provided by in-line coating, it is preferable to perform heat treatment at 70 to 270°C for 3 to 200 seconds, more preferably at 100 to 260°C, and further preferably at 110 to 250°C for 10 to 100 seconds as a target.
[0263] On the other hand, when the resin layer (B) is provided by off-line coating, the heat treatment is preferably performed at 80 to 200°C for 3 to 40 seconds, more preferably at 100 to 180°C for 3 to 40 seconds.
[0264] Regardless of off-line coating or in-line coating, heat treatment and active energy ray irradiation such as ultraviolet ray irradiation may be used together as necessary. The film constituting the release film of the present invention may be subjected to a surface treatment such as corona treatment or plasma treatment in advance.
[0265] <<Lamination structure of release film>>
[0266] The release film in the present invention can form a laminated structure. As a preferred embodiment, a method in which an adhesive layer is laminated on the surface of the resin layer (A) side of the release film can be cited. As a more preferred embodiment, a method in which the release film is used as the first release film, an adhesive layer is laminated on the resin layer (A) side of the release film, and a release film having a release force different from that of the release film is laminated on the other side of the adhesive layer of the release film laminated with the resin layer (A) as the second release film can be cited. As a further preferred embodiment, the adhesive layer is a transparent adhesive sheet for optics (OCA), and the release film is used / laminated as the release film on the side with a lighter release force. It should be noted that the adhesive layer can be a single layer or a structure of more than two layers.
[0267] In addition, the above-mentioned "release film having a release force different from that of the present release film" means that the release force of the release film evaluated by the measurement method described in the Examples is different from the release force of the resin layer (A) side of the present release film. In addition, as a release film having a release force different from that of the present release film, it is preferred that the release force is greater than the release force of the resin layer (A) of the present release film. Specifically, the release force is preferably about 1.5 to 10 times, more preferably 1.5 to 8 times, and further preferably about 1.5 to 6 times. By satisfying the above-mentioned release force, it is possible to reduce the undesirable situation that the resin layer (A) of the present release film is peeled off when it is not necessary to peel it off.
[0268] <Adhesive layer>
[0269] The adhesive layer will be described below.
[0270] The adhesive layer is a layer formed of an adhesive composition, and may be an acrylic adhesive composition with an acrylic resin as the main component, a rubber adhesive composition with rubber as the main component, a urethane adhesive composition with a urethane resin as the main component, or a silicone adhesive composition with a silicone resin as the main component. Among them, the adhesive composition is preferably an acrylic adhesive composition with an acrylic resin as the main component, because the adhesive force and the peeling force can be adjusted in a well-balanced manner and it is inexpensive.
[0271] It should be noted that the above-mentioned "main component resin" refers to the resin with the highest mass ratio among the resins constituting the adhesive composition. For example, it refers to a component that accounts for 50% by mass or more, preferably 60% by mass or more, and more preferably 70% by mass or more of the total amount of the resins constituting the adhesive composition. It should be noted that the upper limit is 100% by mass, but is usually 99.99% by mass.
[0272] (Acrylic resin)
[0273] Examples of the acrylic resin that is a main component resin of the adhesive composition include (meth)acrylic polymers.
[0274] (Meth) acrylic acid series polymer is a polymer with (meth) acrylic acid alkyl ester as main structural unit. As (meth) acrylic acid alkyl ester, for example, methyl (meth) acrylate, ethyl (meth) acrylate, n-propyl (meth) acrylate, isopropyl (meth) acrylate, n-butyl (meth) acrylate, isobutyl (meth) acrylate, sec-butyl (meth) acrylate, tert-butyl (meth) acrylate, n-pentyl (meth) acrylate, n-hexyl (meth) acrylate, isobornyl (meth) acrylate, 4-tert-butyl cyclohexyl (meth) acrylate, tricyclodecyl (meth) acrylate, dicyclopentenyl (meth) acrylate, adamantyl (meth) acrylate, etc. can be cited. They can be used only one kind, and can also be used in combination of two or more kinds. Among these, from the aspect of compatibility with other (meth) acrylates constituting the (meth) acrylic acid series polymer and the heat resistance of the cured resin layer (B), methyl (meth) acrylate is preferred. The content ratio of the (meth)acrylic acid alkyl ester in the monomer forming the (meth)acrylic polymer is, for example, 50% by mass or more, preferably 60 to 99.99% by mass, more preferably 75 to 98.9% by mass, and further preferably 87 to 97.8% by mass. The (meth)acrylic polymer may have a double bond capable of free radical polymerization.
[0275] The (meth)acrylic polymer may be copolymerized with a (meth)acrylate other than the (meth)acrylate alkyl ester, (meth)acrylic acid, or other compounds having a vinyl group in order to improve the glass transition temperature, mechanical properties, compatibility, and the like.
[0276] Examples of (meth)acrylates other than the above-mentioned alkyl (meth)acrylates that can be used as copolymerization components include hydroxyalkyl (meth)acrylates described below, alkoxyalkyl (meth)acrylates such as methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, and ethoxyethyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, glycidyl (meth)acrylate, and γ-butyrolactone (meth)acrylate.
[0277] Examples of the compound having a vinyl group include acrylamide compounds such as dimethylacrylamide, hydroxyethylacrylamide, and dimethylaminopropylacrylamide; styrene compounds such as styrene, α-methylstyrene, and p-methoxystyrene; and maleic anhydride.
[0278] In addition to these, the components (a1) and (a2) described below may also be used appropriately.
[0279] In the present invention, the monomer constituting the (meth)acrylic polymer may contain an acrylic monomer (a1) as a copolymerization component in addition to the (meth)acrylic acid alkyl ester in order to serve as a reaction site with a crosslinking agent described later.
[0280] When the acrylic monomer (a1) is copolymerized with other copolymer components to form an acrylic resin, it becomes a reaction site of a crosslinked structure. It is sufficient to use a monomer containing a functional group that can react with a functional group contained in a crosslinking agent described later. Examples of such acrylic monomers (a1) include hydroxyl-containing monomers, amino-containing monomers, acetoacetyl-containing monomers, isocyanate-containing monomers, glycidyl-containing monomers, and the like. Among these, hydroxyl-containing monomers are preferably used in terms of being able to effectively undergo a crosslinking reaction with a crosslinking agent. One acrylic monomer (a1) may be used alone, or two or more may be used in combination.
[0281] Examples of the hydroxyl group-containing monomer include hydroxyalkyl acrylates such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl 2-hydroxyethyl phthalic acid and N-hydroxymethyl (meth)acrylamide; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate.
[0282] Among the above hydroxyl-containing monomers, primary hydroxyl-containing monomers are preferred in terms of excellent reactivity with a crosslinking agent, and 2-hydroxyethyl acrylate is particularly preferred in terms of having less impurities such as di(meth)acrylate and being easy to produce.
[0283] It should be noted that, as the hydroxyl-containing monomer used in the present invention, it is also preferred to use a di(meth)acrylate containing ratio of 0.5% by mass or less as an impurity, and further preferably to use 0.2% by mass or less, and particularly preferably to use 0.1% by mass or less. As the hydroxyl-containing monomer, specifically, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, etc. are particularly preferred, and they are low molecular weight, and therefore, are preferred in terms of easy purification.
[0284] Examples of the amino group-containing monomer include tert-butylaminoethyl (meth)acrylate, ethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.
[0285] Examples of the acetoacetyl group-containing monomer include 2-(acetoacetoxy)ethyl (meth)acrylate and allyl acetoacetate.
[0286] Examples of the isocyanate group-containing monomer include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, and alkylene oxide adducts thereof.
[0287] Examples of the glycidyl group-containing monomer include glycidyl (meth)acrylate and allyl glycidyl (meth)acrylate.
[0288] The content of the acrylic monomer (a1) in the monomer constituting the (meth) acrylic polymer is preferably 0.01 to 20% by mass, more preferably 0.1 to 10% by mass, and particularly 0.2 to 3% by mass. If the acrylic monomer (a1) is set to be above the above lower limit, the crosslinking site during crosslinking becomes appropriate, and therefore, the cohesive force after crosslinking becomes good. In addition, if it is set to be below the above upper limit, it is possible to prevent the adhesive force from being reduced due to the (a1) component.
[0289] The monomer constituting the (meth)acrylic polymer may contain, in addition to the (meth)acrylic acid alkyl ester or the (meth)acrylic acid alkyl ester and the component (a1), a copolymerizable monomer (a2) other than (a1) as a copolymerization component as necessary.
[0290] Examples of the copolymerizable monomer (a2) include phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, ethoxylated o-phenylphenyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, aromatic ring-containing monomers such as styrene, (meth)acryloylmorpholine, dimethyl (meth)acrylamide, diethyl (meth)acrylamide, amide monomers such as (meth)acrylamide, acrylonitrile, methacrylonitrile, vinyl acetate, vinyl propionate, vinyl stearate, vinyl chloride, ethylenedichloride, alkyl vinyl ether, vinyltoluene, vinylpyridine, vinylpyrrolidone, dialkyl itaconate, dialkyl fumarate, allyl alcohol, acryloyl chloride, methyl vinyl ketone, N-acrylamidomethyltrimethylammonium chloride, allyltrimethylammonium chloride, dimethylallyl vinyl ketone, and the like.
[0291] The content of the copolymerizable monomer (a2) in the monomers forming the (meth)acrylic polymer is preferably 0 to 20% by mass, more preferably 1 to 15% by mass, and particularly preferably 2 to 10% by mass. When the content of the copolymerizable monomer (a2) is within the above range, a decrease in adhesive properties due to the component (a2) can be prevented.
[0292] In the present invention, from the viewpoint of application to foldable displays and imparting flexibility to the pressure-sensitive adhesive layer, 2-ethylhexyl acrylate and / or butyl acrylate are preferably contained.
[0293] The adhesive composition may contain, in addition to the above-mentioned main component resin, a crosslinking agent and other resins constituting the adhesive component (eg, acrylic resin, rubber, silicone resin, polyurethane resin) (other than the main component resin and the crosslinking agent) as required.
[0294] (Crosslinking agent)
[0295] The adhesive composition may contain a crosslinking agent depending on the curing method thereof.
[0296] As the crosslinking agent, for example, isocyanate crosslinking agents, epoxy crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, aldehyde crosslinking agents, amine crosslinking agents, etc. can be cited. Among them, isocyanate crosslinking agents are suitable for improving the adhesion with the substrate or the reactivity with the acrylic resin. The crosslinking agent can be used alone or in combination of two or more.
[0297] The content of the crosslinking agent is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and particularly 0.1 to 3 parts by mass, relative to 100 parts by mass of the main component resin. If the content of the crosslinking agent is within the above range, the cohesive force will not be insufficient, the desired durability can be obtained, and on the other hand, the decrease in flexibility and adhesiveness can be prevented.
[0298] It should be noted that, regarding the curing reaction, in the case of photocuring based on irradiation with active energy rays, it is preferred to mix a multifunctional (meth)acrylate in the adhesive composition as a crosslinking agent. As the above-mentioned multifunctional (meth)acrylate, for example, trimethylolpropane tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, glycerol polyglycidyl ether poly(meth)acrylate, etc. can be cited.
[0299] (Resins constituting other binder components)
[0300] The adhesive composition may contain, in addition to the above-mentioned main component resin and crosslinking agent, a resin constituting an adhesive component other than the main component resin and the crosslinking agent (eg, acrylic resin, rubber, silicone resin, polyurethane resin), as necessary.
[0301] For example, conventionally known additives such as rosin, rosin ester, hydrogenated rosin ester, phenolic resin, aromatic modified terpene resin, aliphatic petroleum resin, alicyclic petroleum resin, styrene resin, and xylene resin, and additives such as tackifiers, silane coupling agents, antistatic agents, colorants, fillers, antioxidants, ultraviolet absorbers, and functional pigments, and compounds that develop or change color when irradiated with ultraviolet rays or radiation can be blended.
[0302] The amount of these additives added is preferably 10% by mass or less, more preferably 5% by mass or less, of the total adhesive composition (based on non-volatile components). In terms of excellent durability, it is preferred that low molecular weight components with a molecular weight of less than 10,000 are not contained as additives as much as possible.
[0303] <Method for forming adhesive layer>
[0304] The method for forming the adhesive layer is not particularly limited, and the adhesive layer can be formed by applying the adhesive composition on the resin layer (A) of the release film, and then drying and curing the adhesive layer as appropriate. Alternatively, the adhesive layer can be formed by applying the adhesive composition on a substrate film or a release film having a release force different from that of the release film, and then drying and curing the adhesive layer as appropriate, and then laminating the release layer (A layer) of the release film on the surface opposite to the surface of the release film having a release force different from that of the release film.
[0305] The adhesive composition may be cured by the crosslinking agent and the main component resin, and may be cured by heating or by irradiation with light such as ultraviolet rays. The adhesive composition may be appropriately diluted with an organic solvent and applied to a release layer or the like.
[0306] <Adhesive layer characteristics>
[0307] (Thickness of adhesive layer)
[0308] The thickness of the adhesive layer is not particularly limited. For example, from the perspective of imparting sufficient adhesive force or filling the unevenness and height difference of the substrate to which the adhesive is bonded, it is preferably 0.1 μm or more, more preferably 0.5 μm or more, and more preferably 1 μm or more. On the other hand, from the perspective of material use efficiency, transmittance, and exhaust, it is preferably 10000 μm or less, more preferably 3000 μm or less, and more preferably 1000 μm or less.
[0309] (Elastic modulus of adhesive layer)
[0310] In the present invention, the elastic modulus of the adhesive layer at 25°C is preferably 6.0MPa or less. The so-called elastic modulus here is a value measured by a nanoindenter. By making the elastic modulus below 6.0MPa, the adhesive layer has good followability to deformation and can be used for foldable display applications. From these viewpoints, the elastic modulus of the adhesive layer is more preferably below 5.0MPa, further preferably below 4.0MPa, and particularly below 3.0MPa. In addition, from the viewpoint of the formability of the adhesive layer, the elastic modulus of the adhesive layer at 25°C is preferably above 0.5MPa, more preferably above 1.0MPa, and further preferably above 1.5MPa.
[0311] (Glass transition temperature (Tg) of adhesive layer)
[0312] The glass transition temperature was calculated according to the following Fox equation.
[0313]
[0314] Tg: glass transition temperature of copolymer (K)
[0315] Tga: Glass transition temperature of the homopolymer of monomer A (K)
[0316] Wa: Weight fraction of monomer A
[0317] Tgb: Glass transition temperature of the homopolymer of monomer B (K)
[0318] Wb: weight fraction of monomer B
[0319] Tgn: Glass transition temperature of the homopolymer of monomer N (K)
[0320] Wn: Weight fraction of monomer N
[0321] (Wa+Wb+···+Wn=1)
[0322] In the present invention, considering the application to foldable displays, Tg is preferably in the range of -55°C to -70°C, and more preferably in the range of -58°C to -68°C.
[0323] By satisfying the above range, an adhesive layer having good followability to deformation such as bending can be obtained.
[0324] <<How to use the film laminate>>
[0325] This film laminate can be used in various laminated structures. For example, the release film with an adhesive layer can be formed into a film laminate with an optical component attached to the surface of the adhesive layer. This film laminate can be made by peeling off the adhesive layer exposed by the release film to make the optical component attached to the adherend. As the optical component, for example, a polarizing plate, a touch sensor, etc. can be cited. In addition, it can also be a vehicle-mounted optical component such as a touch panel mounted on a car.
[0326] (Polarizing plate)
[0327] The material and structure of the polarizing plate are arbitrary, for example, a TAC (triacetyl cellulose) film as a protective film is laminated on a stretched polyvinyl alcohol film using iodine as an orientation pigment, and is widely used as such a polarizing plate. In addition, the polarizing plate may have the following layer structure: it has a hard coating having substantially no phase difference on the surface, anti-glare, low reflection, antistatic and other functions.
[0328] (Touch Sensor)
[0329] A touch sensor is a component that detects the touch location when a user touches an image displayed on a screen with a finger, a stylus, or the like. Depending on the sensor technology, there are examples of methods such as an electrostatic capacitance method, a resistive film method, and a surface wave method using infrared rays or ultrasonic waves.
[0330] Generally, a touch sensor is mounted on a display device such as a liquid crystal display panel or an organic EL.
[0331] In recent years, there has been a trend to use a base film as a substitute for a glass substrate, with a focus on flexibility, and a touch sensor film is preferably used. A touch sensor film is generally provided with a patterned transparent conductive layer for performing the function of a sensing electrode.
[0332] In addition, the film laminate comprises the release film with the adhesive layer and other release films, and may have a layer structure in which the release film with the adhesive layer is attached to the other release film via the adhesive layer. The film laminate having such a layer structure comprises the release film / adhesive layer / other release film, and can be used as a double-sided adhesive sheet.
[0333] The other release film has a release layer formed on the surface of a base material such as a resin film, and the surface having the release layer formed is preferably bonded to the adhesive layer. The release layer of the other release film is preferably other than the above-mentioned release layer.
[0334] In the film laminate having the above structure, the ratio (MB / MA) of the elastic modulus (MA) of the release layer of the present release film to the elastic modulus (MB) of the release layer of other release films is preferably in the range of 4 to 30, and more preferably in the range of 4 to 25. When the elastic modulus satisfies the above range, the defect of peeling of the present release film can be reduced when peeling is not required in the film laminate.
[0335] For the film laminate with other release films attached, it is appropriate to peel off the release film and make the exposed adhesive layer surface of the remaining release film with adhesive layer be attached to the optical component for use. Then, it is appropriate to peel off other release films from the adhesive layer of the release film with adhesive layer. In addition, it is also possible to adhere the release film to the aforementioned adhesive layer attached to the optical component again. In this way, the release film of the present invention is ultra-lightly releasable and has low migration, so it can also be used by re-peeling the so-called release film.
[0336] It should be noted that for other release films, the normal peeling force measured by peeling at 180° at a peeling speed of 0.3 m / min is greater than the normal peeling force of the present release film, specifically, preferably about 2 to 10 times the normal peeling force of the present release film, and more preferably 2 to 6 times. By satisfying the above-mentioned peeling force ratio, the undesirable situation that the present release film peels when it is not necessary to peel can be reduced.
[0337] The release film and the film laminate are preferably used for vehicle mounting. When used for vehicle mounting, the adhesive strength of the adhesive layer needs to be improved in order to maintain high adhesive strength even when exposed to a high temperature atmosphere in summer or a low temperature environment in winter. The release film can achieve ultra-light peeling properties, so even if the adhesive strength of the adhesive layer is high, the peeling performance becomes good.
[0338] <<<Explanation of terms, etc.>>>
[0339] In the present invention, when referred to as a "film", it also includes a "sheet", and when referred to as a "sheet", it also includes a "film".
[0340] In addition, when the term "panel" is used, such as an image display panel, a protection panel, a touch panel, etc., it includes a plate body, a sheet, and a film.
[0341] In the present invention, when "X to Y" (X and Y are arbitrary numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", and the meaning of "preferably greater than X" or "preferably less than Y".
[0342] In addition, when described as "X or more" (X is an arbitrary number), unless otherwise specified, it includes the meaning of "preferably greater than X", and when described as "Y or less" (Y is an arbitrary number), unless otherwise specified, it also includes the meaning of "preferably less than Y".
[0343] Example
[0344] Hereinafter, the present invention will be described in further detail with reference to Examples, but the present invention is not limited to the following Examples unless the gist thereof is exceeded. The evaluation methods in Examples and Comparative Examples are as follows.
[0345] (1) Method for determining intrinsic viscosity of polyester
[0346] 1 g of polyester from which other polymer components and pigments incompatible with the polyester were removed was precisely weighed, 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio) was added and dissolved, and the measurement was performed at 30°C.
[0347] (2) Method for measuring average particle size (d50: μm)
[0348] The average particle size was determined as a value of 50% cumulative (based on mass) in an equivalent spherical distribution measured using a centrifugal sedimentation particle size distribution analyzer (SA-CP3 model, manufactured by Shimadzu Corporation).
[0349] (3) Method for measuring film thickness of resin layer (A)
[0350] In order to suppress reflection from the back side, a black tape (VINYL TAPE VT-50 manufactured by NICHIBANCo., Ltd.) was attached to the back side of the sample film in advance. A spectrophotometer (UV-visible spectrophotometer "V-670" manufactured by JASCO Corporation) was used in the measurement to measure the absolute reflectivity in the wavelength range of 300 to 800 nm under the conditions of synchronous mode, incident angle 5°, N polarization, Fast response, data acquisition interval 1.0 nm, bandwidth 10 nm, and scanning speed 1000 m / min. The film thickness was obtained by comparing the data obtained in the measurement with the data calculated based on the refractive index of silicone being 1.43.
[0351] (4) Method for measuring film thickness of resin layer (B) and primer layer
[0352] The surface of the cured resin layer (B) was dyed with RuO4 and embedded in epoxy resin. Then, the slices prepared by ultrathin sectioning were dyed with RuO4 and the cross section of the coating layer was measured by TEM (H-7650 manufactured by Hitachi High-Tech Corporation, accelerating voltage 100 kV).
[0353] (5) Determination of surface resistivity
[0354] The surface resistivity was measured using a low resistivity meter ("Loresta GP MCP-T600" manufactured by Mitsubishi Chemical Corporation) in a measurement atmosphere at a temperature of 23°C and a relative humidity of 50% for 30 minutes after humidity conditioning the sample, and the value after 1 minute was taken as the surface resistivity. If the upper limit of the measurable resistance value range was exceeded, it was recorded as unmeasurable.
[0355] (6) Determination of average surface roughness
[0356] The arithmetic mean roughness (Ra) of the resin layer (B) was measured using a surface roughness meter (manufactured by Kosaka Laboratory Co., Ltd., two-dimensional roughness meter "surfcorder SE3500") in accordance with JIS B 0601-2001. In addition, the maximum cross-sectional height (Rt) of the anti-release surface was measured. Rt can be obtained as the sum of the maximum value of the peak height Rp and the maximum value of the valley depth Rv of the roughness curve of the evaluation length.
[0357] (7) Molecular weight determination of curable silicone resin
[0358] A GPC measuring device was used to measure the chromatogram, and the number average molecular weight (Mn) and the mass average molecular weight (Mw) were obtained based on the standard curve using standard polystyrene, as shown in Table 2. Specifically, 4 mg of the sample for measurement was dissolved in 4 mL of THF, and 100 μL of the measurement solution was injected into the GPC measuring device as the measurement solution and measured. Tetrahydrofuran (THF) was used as the eluent. "Ecosec8320" manufactured by Tosoh Corporation was used in the analysis, and "TSKgelguardcolumn HXL-L" manufactured by Tosoh Corporation was used as the guard column. Four "TSKgel GMHXL" manufactured by Tosoh Corporation were connected and used for the column. In addition, the analysis was carried out under the conditions of an oven temperature of 40°C and a THF flow rate of 1.0 mL / min, and RI was used in the detection.
[0359] (8) Composition analysis of curable silicone resin
[0360] The composition analysis of the curable silicone resin used in Examples and Comparative Examples was performed using 400 MHz-NMR (Bruker Avance 400M). 1 In the H-NMR measurement, CDCl 3 was used as a solvent, and the peak derived from the methyl group of dimethylsiloxane was used as a chemical shift standard, and the measurement was performed at a temperature of 30°C.
[0361] (9) Measurement of normal peeling force of resin layer (A)
[0362] The resin layer (A) surface of the sample film was pressed with a rubber roller (2 kg) (reciprocating twice), and an adhesive tape (Tesa "No. 7475") was attached, and then cut into a size of 25 mm × 300 mm, and the peeling force after leaving it at room temperature (23° C.) for 1 hour was measured. The peeling force was measured as follows: Using "Intesco Model 2001" manufactured by INTESCO Co., Ltd., the sample film was peeled at 180° under the condition of a tensile speed of 0.3 m / min.
[0363] (10) Measurement of Residual Adhesion Rate of Resin Layer (A) (Evaluation of Migration)
[0364] The sample film was cut into A4 size (210 mm × 297 mm), and a 75 μm biaxially stretched PET film (DIAFOIL T100-75 manufactured by Mitsubishi Chemical Corporation) was stacked on the release layer (A layer) and pressed for 2 hours at a temperature of 23°C and a pressure of 1 MPa. The "75 μm biaxially stretched PET film" was used alone as an evaluation film.
[0365] On the other hand, the same "75 μm biaxially stretched PET film" as above was overlapped on an untreated base film without a resin layer (A), and pressed under the same conditions as above, and the "75 μm biaxially stretched PET film" alone was used as the reference film.
[0366] An adhesive tape (“No. 31B” manufactured by Nitto Denko Corporation) was adhered by pressing (reciprocating twice) the contact surface of the evaluation film with the sample film (resin layer (A) (A layer)) and the contact surface of the reference film with the substrate film using a rubber roller (2 kg), and then cut into a size of 50 mm × 300 mm, and the peeling force after being left at room temperature for 1 hour was measured.
[0367] The peeling force was measured by peeling the evaluation film and the reference film at 180 degrees at a tensile speed of 0.3 m / min using "Intesco Model 2001" manufactured by INTESCO Co., Ltd.
[0368] Then, the measured peeling force of the evaluation film and the peeling force of the reference film were substituted into the following formula to determine the residual adhesion ratio (%). It should be noted that the values here are values without heat treatment or the like.
[0369] Residual adhesion rate (%) = (peel strength of evaluation film / peel strength of reference film) × 100
[0370] In a film with high mobility, a large amount of silicone adheres to the overlapping film, so the peeling force of the adhesive tape becomes small and the residual adhesion rate (%) also decreases. Therefore, the mobility of the resin layer (A) of the release film is evaluated as follows based on the value of the residual adhesion rate.
[0371] (11) Re-peeling rate of resin layer (A) after pressing (alternative evaluation of adhesion)
[0372] An acrylic adhesive tape (Tesa "No. 7475") was attached to the resin layer (A) surface of the release film of the Example and the Comparative Example, and then cut into a size of 25 mm x 150 mm and left at room temperature for 1 hour. The peeling force at 180° under a tensile speed of 0.3 m / min was taken as (F1).
[0373] Next, the other side (in the present invention, the resin layer (B) side) is placed on the resin layer (A) side of the release film of the embodiment and the comparative example in a manner of facing each other, and a pressing treatment is performed for 20 hours at a temperature of 40°C, a humidity of 90% RH, and a load of 1 MPa. An acrylic adhesive tape (Tesa's "No.7475") is adhered to the treated resin layer (A) side, cut into a size of 25 mm × 150 mm, and left at room temperature for 1 hour. The peeling force at 180° peeling under a tensile speed of 0.3 m / min is taken as (F2).
[0374] The re-peelability after pressing was calculated according to the following formula, and the re-peelability at this time was used as an index of anti-blocking property. It should be noted that the smaller the re-peelability, the better the anti-blocking property was judged to be.
[0375] Re-peeling rate after pressing (%) = (F2-F1) / F1×100
[0376] (12) Adhesion evaluation
[0377] The release films of the examples and comparative examples were arranged so that the release surface and the reverse release surface faced each other, and were pressed by a press machine at a pressure of 10 kg / cm 2 , 40°C, 80%RH atmosphere, and pressurized for 20 hours to obtain a sample for anti-blocking evaluation. Afterwards, a peeling device ("AGI" manufactured by Shimadzu Corporation) was used to measure the peeling force under the conditions of a tensile speed of 300 mm / min and 180° peeling, and the peeling force at this time was used as an index of anti-blocking. It should be noted that the smaller the peeling force, the better the anti-blocking property.
[0378] 《Evaluation Criteria》
[0379] A (good): The peeling force is 20 g / 25 mm or less, and peeling can be performed without any problem.
[0380] B (poor): The peel force exceeded 20 g / 25 mm and blocking occurred.
[0381] (13) Adhesion between substrate film and resin layer (A)
[0382] The sample film was placed in a constant temperature and humidity chamber at 60°C and 80% RH for 4 weeks, then taken out. The resin layer (A) surface of the sample film was rubbed 5 times with a hand, and the adhesion was evaluated according to the degree of release layer peeling using the following evaluation criteria.
[0383] 《Evaluation Criteria》
[0384] ○: The coating film did not turn white and did not fall off.
[0385] ×: The coating film turned white or peeling was observed.
[0386] (14) Measurement of normal peeling force of resin layer (B)
[0387] An acrylic adhesive tape (Tesa "No. 7475") was attached to the resin layer (B) of the sample film by pressing (reciprocating twice) with a rubber roller (2 kg), and then cut into a size of 25 mm × 150 mm, and the peeling force was measured after leaving it at room temperature (23° C.) for 1 hour. The peeling force was measured as follows: Using "Intesco Model 2001" manufactured by INTESCO Co., Ltd., the sample film was peeled at 180° under a tensile speed of 0.3 m / min.
[0388] (15) Determination of surface free energy of resin layer
[0389] In a measurement atmosphere of 23°C and 50 RH%, a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., trade name "DMo-501") was used to make drops of ion exchange water and diiodomethane on the resin layer of the sample film, and the contact angle was measured. The contact angle was measured as follows: the contact angle 60 seconds after each liquid was dropped onto the laminated polyester film.
[0390] The contact angle data of ion-exchanged water and diiodomethane obtained by this method were used to calculate the surface free energy of the antireflection layer surface using the surface tension component values of each solvent (Table 1) according to the Owens-Wendt theory.
[0391] [Table 1]
[0392] Table 1
[0393] Solvents Surface tension (mN / m) Dispersion component (mN / m) Polar component (mN / m) Ion exchange water 72.8 21.8 51 Diiodomethane 50r8 50.8 0
[0394] (16) Measurement of elastic modulus of resin layer (A)
[0395] The elastic modulus of the resin layer (A) at a point with an indentation depth of 50 nm was measured at room temperature (25° C.) using a nanoindenter (TI 950 TriboIndenter) manufactured by Hysitron Corporation.
[0396] (17) Measurement of elastic modulus of adhesive layer
[0397] The elastic modulus of the adhesive layer at a point with an indentation depth of 500 nm was measured using a nanoindenter (TI 950 TriboIndenter) manufactured by Hysitron Corporation with an indenter (conical: spherical, radius of curvature: 10 μm) at room temperature (25° C.).
[0398] (18) Adhesive peel strength
[0399] The adhesive composition described in Table 8 was applied to the release layer of the sample film to a film thickness of 2 mil in a wet state, and cured by heating at 150°C for 3 minutes to form an adhesive layer (thickness (after drying) 20 μm).
[0400] After that, another release film is laminated on the adhesive layer to obtain a film laminate consisting of a sample film / adhesive layer / other release film. It should be noted that the release films prepared in Comparative Examples 1 to 4 described later are used as other release films. In the obtained film laminate, the peeling force when the sample film is peeled off from the adhesive layer is measured. The peeling force is measured as follows: using "Intesco Model 2001" manufactured by INTESCO Co., Ltd., the peeling is performed at 180° under the condition of a tensile speed of 0.3 m / min.
[0401] The polyesters used in Examples and Comparative Examples were prepared as follows.
[0402] <Method for producing polyester (A)>
[0403] 100 parts by mass of dimethyl terephthalate and 60 parts by mass of ethylene glycol were used as starting materials, and 0.09 parts by mass of magnesium acetate tetrahydrate as a catalyst was taken in the reactor, and the reaction starting temperature was set to 150°C. While methanol was distilled off, the reaction temperature was slowly raised to 230°C after 3 hours. After 4 hours, the transesterification reaction was substantially completed. After adding 0.04 parts by mass of ethyl acid phosphate to the reaction mixture, 0.04 parts by mass of antimony trioxide was added, and a 4-hour polycondensation reaction was carried out. That is, the temperature was slowly raised from 230°C to 280°C. On the other hand, the pressure was slowly reduced from normal pressure to 0.3 mmHg. After the reaction started, the reaction was stopped at a time corresponding to a characteristic viscosity of 0.65 according to the change in the stirring power of the reaction tank, and the polymer was discharged under nitrogen pressure to obtain a polyester (A) with a characteristic viscosity of 0.65.
[0404] <Method for producing polyester (B)>
[0405] In the method for producing polyester (A), polyester (B) was obtained by the same method as the method for producing polyester (A), except that 0.04 parts by mass of ethyl acid phosphate was added, 0.2 parts by mass of silica particles having an average particle size of 2.3 μm dispersed in ethylene glycol and 0.04 parts by mass of antimony trioxide were added, and the polycondensation reaction was stopped at a point corresponding to an intrinsic viscosity of 0.65. The intrinsic viscosity of the obtained polyester (B) was 0.65.
[0406] Example 1-1
[0407] A mixed raw material in which polyesters (A) and (B) were mixed in a ratio of 90% by mass and 10% by mass, respectively, was used as the raw material for the outermost layer (surface layer), and polyester (A) was used as the raw material for the middle layer. Each was supplied to two extruders, and after each was melted at 290°C, it was co-extruded on a cooling roll set at 25°C with a layer structure of two kinds of three layers (surface layer / middle layer / surface layer = 1:18:1 discharge amount), and cooled and solidified to obtain an unstretched sheet. Then, by utilizing the roller peripheral speed difference, the film was stretched 3.4 times in the longitudinal direction at a film temperature of 85°C, and then the coating liquid 1 of the resin layer (B) shown in Table 4 was coated on one side of the longitudinally stretched film, and the following primer composition was coated on the other side, and introduced into a tenter, stretched 4.5 times in the transverse direction at 120°C, and after heat treatment at 225°C, relaxed 2% in the transverse direction to obtain a biaxially stretched polyester film with a thickness of 50 μm, a film thickness of the resin layer (B) (after drying) of 0.05 μm, and a film thickness of the primer layer (after drying) of 0.05 μm.
[0408] Next, the coating solution 1 for the resin layer (A) shown in Table 3 was applied onto the primer layer surface of the obtained polyester film as the resin layer (A) using a No. 4 rod by a rod coating method in such a manner that the coating amount (after drying) had a thickness of 1.0 μm, and then dried at 150° C. for 30 seconds to obtain a release film.
[0409] Embodiments 1-2 to 1-12:
[0410] A mold release film was obtained in the same manner as in Example 1-1 except that coating solutions 2 to 12 of the resin layer (B) shown in Table 4 were applied to one side of the longitudinally stretched film.
[0411] The obtained release film is shown in Table 4. The thickness of the resin layer (A) is thin and the elastic modulus is 500 MPa or less. On the other hand, the resin layer (B) contains a non-silicone release agent, thereby achieving ultra-light release to a release force (normal release force) of 5 g / 25 mm or less, and taking into account the anti-blocking property to a heavy release rate after pressing of 100% or less. In addition, the substrate adhesion is good and the migration is low.
[0412] Examples 1-13 to 1-28
[0413] A mixed raw material in which polyesters (A) and (B) were mixed in a ratio of 97% by mass and 3% by mass respectively was used as the raw material for the outermost layer (surface layer), and polyester (A) was used as the raw material for the middle layer. They were supplied to two extruders respectively, and after each was melted at 290°C, they were co-extruded on a cooling roll set at 25°C in a layer structure of two kinds of three layers (discharge amount of surface layer / middle layer / surface layer=1:18:1), and cooled and solidified to obtain an unstretched sheet. Then, by utilizing the roller peripheral speed difference, the film was stretched 3.4 times in the longitudinal direction at a film temperature of 85°C, and then the coating solution of the resin layer (B) shown in Table 4 was coated on one side of the longitudinally stretched film, and the following primer composition was coated on the other side, and introduced into a tenter, stretched 4.5 times in the transverse direction at 120°C, and after heat treatment at 225°C, relaxed 2% in the transverse direction to obtain a biaxially stretched polyester film with a thickness of 50 μm, a film thickness of the resin layer (B) (after drying) of 0.05 μm, and a film thickness of the primer layer (after drying) of 0.05 μm.
[0414] Next, the coating liquid 1 of the resin layer (A) shown in Table 3 was applied on the primer surface of the obtained polyester film as the resin layer (A) by a No. 4 rod by a rod coating method in such a manner that the coating amount (after drying) had a thickness of 1.0 μm, and then dried at 150° C. for 30 seconds to obtain a release film.
[0415] The obtained release film is shown in Table 5. The thickness of the resin layer (A) is thin and the elastic modulus is 500 MPa or less. On the other hand, the resin layer (B) contains a non-silicone release agent, thereby achieving ultra-light release to a release force (normal release force) of 5 g / 25 mm or less, and taking into account the anti-blocking property to a heavy release rate after pressing of 100% or less. In addition, the substrate adhesion is good and the migration is low.
[0416] Comparative Example 1-1
[0417] A release film was obtained in the same manner as in Example 1-1 except that the resin layer (B) and the primer layer were not provided on the longitudinally stretched film.
[0418] Comparative Example 1-2
[0419] A release film was obtained in the same manner as in Example 1-1 except that the resin layer (B) was not provided on the longitudinally stretched film.
[0420] As shown in Table 5, the release films of Comparative Examples 1-1 and 1-2 obtained had a high re-peelability rate after pressing because there was no resin layer (B) containing a non-silicone release agent, and there was a concern about the occurrence of blocking.
[0421] Comparative Examples 1-3
[0422] In Example 1-1, except that the resin layer (B) composition was changed to the coating liquid 13 not containing a non-silicone-based release agent, the same procedure as in Example 1 was carried out to obtain a release film.
[0423] The obtained release film is shown in Table 5. Since the resin layer (B) does not contain a non-silicone release agent, the re-peeling rate after pressing becomes high, and there is a concern that blocking may occur.
[0424] Comparative Examples 1-4
[0425] A mold release film was obtained in the same manner as in Example 1 except that the coating liquid 2 of the resin layer (A) was used in Example 1-1.
[0426] As shown in Table 5, the obtained release film had a thin resin layer (A) and a high elastic modulus, so the peeling force (normal peeling force) was about 3 times as high as that of Examples 1-1 to 1-12, and ultralight peeling could not be achieved. In addition, the substrate adhesion was poor.
[0427] Reference Example 1
[0428] A release film was obtained in the same manner as in Example 1 except that the coating liquid 3 (particle content: 0.19 mass %) of the resin layer (A) was used.
[0429] The obtained release film was shown in Table 5. The presence of particles made the resin layer (A) brittle, so the substrate adhesion was poor, and the mobility was high due to the falling of particles. In addition, the re-peeling rate after pressing was high, and there was a concern about blocking.
[0430] Examples of the compounds constituting the resin layer (A) are as follows.
[0431] a1: curable silicone resin (silicone resin having vinyl groups introduced into the side chains and / or terminals of the main chain containing siloxane bonds, number average molecular weight: 10,600, viscosity at 25° C. when diluted with n-heptane solvent to 15% by mass: 1.7 mcps)
[0432] a2: A mixture containing a curable silicone resin (a silicone resin having vinyl groups introduced into the side chains and / or the terminals of the main chain containing siloxane bonds, number average molecular weight: 364,000) and a silicone crosslinking agent (a silicone resin having Si—H groups introduced into the side chains and / or the terminals of the main chain containing siloxane bonds) (viscosity at 25° C. when diluted with an n-heptane solvent to adjust to 15% by mass: 410 mcps)
[0433] The content ratio (mol %) of each functional group in the curable silicone resin is as follows.
[0434] [Table 2]
[0435] Table 2
[0436] Functional Group a1 a2 methyl 99.0 99.0 H 0.0 0.7 Vinyl 1.0 0.3
[0437] b1: Silicone crosslinking agent (CL750: manufactured by Momentive Performance Materials, Inc.)
[0438] c1: Addition type platinum catalyst (CM678: manufactured by Momentive Performance Materials, Inc.)
[0439] c2: Addition type platinum catalyst (PL-50T: manufactured by Shin-Etsu Chemical Co., Ltd.)
[0440] d1: Particles (Tospearl 120: manufactured by Momentive Performance Materials, Inc.)
[0441] The coating liquid constituting the resin layer (A) is as follows.
[0442] [Table 3]
[0443] Table 3
[0444]
[0445] Examples of the compounds constituting the resin layer (B) and the primer layer are as follows.
[0446] (Release Agent)
[0447] AI: Compounds containing long-chain alkyl groups
[0448] In a four-necked flask, 200 parts of xylene and 600 parts of octadecyl isocyanate were added and heated under stirring. From the moment when xylene began to reflux, 100 parts of polyvinyl alcohol with an average degree of polymerization of 500 and a saponification degree of 88 mol% were added in small amounts at intervals of 10 minutes over about 2 hours. After the addition of polyvinyl alcohol was completed, reflux was further performed for 2 hours to terminate the reaction. After the reaction mixture was cooled to about 80°C, it was added to methanol. As a result, the reaction product precipitated in the form of a white precipitate. Therefore, the precipitate was filtered off, 140 parts of xylene was added, and after heating to completely dissolve it, methanol was added again to precipitate. After repeating this operation several times, the precipitate was washed with methanol, dried and crushed, and obtained.
[0449] AII: Wax
[0450] In an emulsifying device with a capacity of 1.5 L and equipped with a stirrer, a thermometer and a temperature controller, 300 g of oxidized polyethylene wax with a melting point of 105° C., an acid value of 16 mgKOH / g, a density of 0.93 g / mL and an average molecular weight of 5000, 650 g of ion exchange water, 50 g of decaglycerol monooleate surfactant and 10 g of a 48% potassium hydroxide aqueous solution were added. The system was substituted with nitrogen, sealed and stirred at high speed at 150° C. for 1 hour, cooled to 130° C., and passed through a high-pressure homogenizer at 400 atmospheres to obtain a wax emulsion cooled to 40° C.
[0451] (Antistatic Agent)
[0452] BI: Conductive agent composed of polyethylene dioxythiophene and polystyrene sulfonic acid (Orgacon ICP1010 manufactured by Agfa-Gevaert) neutralized with concentrated ammonia to a pH of 9, non-volatile component; 1.2 mass%, solvent; water
[0453] (Polyhydroxy compounds)
[0454] CI: polyglycerol with an average of n=4 in the above formula (9)
[0455] CII: A compound in which an average of 4 molecules of polyethylene oxide are added to a polyglycerol backbone in which n=2 in the above formula (9).
[0456] (Binder)
[0457] DI: Aqueous dispersion of polyester resin copolymerized with the following composition
[0458] Monomer composition: (acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfoisophthalate / / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)
[0459] DII: A polyurethane resin aqueous dispersion prepared by polymerization with the following composition:
[0460] When a polyester polyol composed of 282 parts by mass of terephthalic acid, 282 parts by mass of isophthalic acid, 62 parts by mass of ethylene glycol, and 250 parts by mass of neopentyl glycol is referred to as (C1a), a polyester polyurethane composed of 876 parts by mass of (C1a), 244 parts by mass of toluene diisocyanate, 81 parts by mass of ethylene glycol, and 67 parts by mass of dimethylol propionic acid is neutralized with ammonia and dispersed in water (concentration 20%, viscosity 50 mPa·s at 25° C.)
[0461] (Crosslinking agent)
[0462] EI: Hexamethoxymethylolmelamine
[0463] EII: Acrylic polymer with oxazoline group and polyalkylene oxide chain
[0464] Epocros (oxazoline base amount = 4.5 mmol / g, manufactured by Nippon Shokubai Co., Ltd.)
[0465] (Surfactant)
[0466] FI: A nonionic surfactant represented by the following formula and having a polyethylene oxide structure in a side chain.
[0467]
[0468] In the above formula, m and n are integers representing the number of moles of ethylene oxide added, and the average of m+n is 10.
[0469] The coating liquid constituting the resin layer (B) is as follows. In addition, Table 3 shows the amount based on the non-volatile component.
[0470] [Table 4]
[0471] Table 4
[0472]
[0473] <Undercoat composition>
[0474] The coating liquid constituting the undercoat layer is as follows.
[0475] (BI) / (CII) / (DII) / (FI)=10 mass% / 35 mass% / 50 mass% / 5 mass% [Table 5]
[0476]
[0477] <Method for producing polyester (1)>
[0478] 100 parts by mass of dimethyl terephthalate and 55 parts by mass of ethylene glycol were used as starting materials, and 0.04 parts by mass of magnesium acetate tetrahydrate as a catalyst was taken into the reactor, and the reaction starting temperature was set to 150°C. While methanol was distilled off, the reaction temperature was slowly raised to 230°C after 3 hours. After 4 hours, the transesterification reaction was substantially completed. After adding 0.02 parts by mass of ethyl acid phosphate to the reaction mixture, 0.04 parts by mass of antimony trioxide was added, and a polycondensation reaction was carried out for 4 hours. That is, the temperature was slowly raised from 230°C to 280°C. On the other hand, the pressure was slowly reduced from normal pressure to 0.3 mmHg. After the reaction started, the reaction was stopped at a time corresponding to an intrinsic viscosity of 0.59 dl / g according to the change in the stirring power of the reaction tank, and the polymer was discharged under nitrogen pressure to obtain a polyester (1) with an intrinsic viscosity of 0.59 dl / g.
[0479] <Method for producing polyester (2)>
[0480] 100 parts by mass of dimethyl terephthalate and 45 parts by mass of ethylene glycol were used as starting materials. 0.06 parts by mass of magnesium acetate tetrahydrate as a catalyst was placed in a reactor. The reaction start temperature was set to 150°C. While methanol was distilled off, the reaction temperature was slowly raised to 230°C after 3 hours. After 4 hours, the transesterification reaction was substantially completed. After adding 0.03 parts by mass of ethyl acid phosphate to the reaction mixture, 0.3 parts by mass of silica particles with an average particle size of 2.7 μm dispersed in ethylene glycol and 0.03 parts by mass of antimony trioxide were added, and a polycondensation reaction was carried out for 4 hours. That is, the temperature was slowly raised from 230°C to 280°C. On the other hand, the pressure was slowly reduced from normal pressure to 0.3 mmHg at the end. After the reaction started, the reaction was stopped at a time corresponding to an intrinsic viscosity of 0.59 dl / g according to the change in the stirring power of the reaction tank. The polymer was discharged under nitrogen pressure to obtain a polyester (2) with an intrinsic viscosity of 0.59 dl / g.
[0481] <Method for producing polyester (3)>
[0482] Polyester (3) having an intrinsic viscosity of 0.60 dl / g was obtained in the same manner as polyester (2) except that 10 parts by mass of organic particles (styrene-divinylbenzene: styrene resin) having an average particle size of 4.5 μm were added instead of silica particles.
[0483] <Method for producing polyester film>
[0484] [PET-A]
[0485] A blend of polyester (1) and polyester (2) at a mass ratio of 80 / 20 as a raw material for layer A, polyester (1) alone as a raw material for layer B, and a blend of polyester (1) and polyester (3) at a mass ratio of 95.5 / 4.5 were supplied to a layer C extruder, heated and melted at 285°C, and co-extruded under extrusion conditions so that the thickness composition ratio was A / B / C = 5 / 90 / 5 in a layer composition of three layers (A (layer A) / B (layer B) / C (layer C)) with layer A and layer C as the outermost layers (surface layers) and layer B as the intermediate layer, and cooled and solidified while being in close contact with a mirror-cooled drum having a surface temperature of 40 to 50°C to prepare an unstretched polyethylene terephthalate film. The film was stretched 3.0 times in the longitudinal direction while passing through a heated roll group at 85°C to prepare a uniaxially oriented film. For the uniaxially stretched film, the cured resin layer composition shown below is coated on both sides, and then the film is introduced into a tenter stretching machine, stretched 4.1 times in the width direction at 100°C, and then heat treated at 235°C, and then relaxed by 2% in the width direction to obtain a biaxially oriented polyester film with a thickness of 50 μm and a cured resin layer with a film thickness (after drying) of 0.05 μm on both sides.
[0486] (Cured resin layer composition)
[0487] (A): Thiophene antistatic agent
[0488] A conductive agent composed of polyethylene dioxythiophene and polystyrene sulfonic acid, "Orgacon ICP1010" manufactured by Agfa-Gevaert, was neutralized with concentrated aqueous ammonia to adjust the pH to 9.
[0489] (B) Polyhydroxy compounds
[0490] Polyglycerol with an average degree of polymerization of 4
[0491] (C) Aqueous dispersion of a polyester resin having a condensed polycyclic structure copolymerized with the following composition:
[0492] Monomer composition: (acid component) 2,6-naphthalene dicarboxylic acid / sodium 5-sulfonate of isophthalic acid / / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)
[0493] A / B / C=7 / 10 / 83 (mass %)
[0494] <Mold release layer composition>
[0495] a1: Curable silicone resin (a silicone resin having vinyl groups introduced into the side chains and / or terminals of the main chain formed by siloxane bonds, number average molecular weight: 10,600, viscosity at 25° C. when diluted with n-heptane solvent to 15% by mass: 1.7 mcps)
[0496] (Composition Analysis of Curable Silicone Resin)
[0497] The 400 MHz-NMR (Bruker Avanc e The composition analysis of the curable silicone resins used in the Examples / Comparative Examples was performed at 400 M, and the results are shown in Table 1. 1 H-NMR measurement was performed using CDCl 3 as a solvent and a peak derived from the methyl group of dimethylsiloxane as a chemical shift standard at a temperature of 30° C. Table 1 below shows the content ratio (mol %) of each functional group in the curable silicone resin.
[0498] [Table 6]
[0499] Table 6
[0500] Functional Group a1 methyl 98.9 H 0 Vinyl 1.1
[0501] b1: Cross-linking agent (CL750: manufactured by Momentive Performance Materials, Inc.)
[0502] c1: Addition type platinum catalyst (CM678: manufactured by Momentive Performance Materials, Inc.)
[0503] e1: Light stripping agent (methylphenyl silicone oil, Mw: less than 10,000, phenyl content ratio; DM:MP=91:9 (mol%))
[0504] e2: Light stripping agent (methylphenyl silicone oil, Mw: 21000 phenyl content ratio; DM:MP = 91:9 (mol%))
[0505] e3: Light stripping agent (methylphenyl silicone oil, Mw: 71000 phenyl content ratio; DM:MP = 90:10 (mol%))
[0506] e4: Light release agent BY24-850 (manufactured by Dow Toray Co., Ltd.) (polydimethylsiloxane, Mw: 100,000 or more, phenyl content ratio; DM:MP=100:0 (mol%))
[0507] [Example 2-1]
[0508] The coating amount (after drying) is 1 g / m2 The following release layer composition was applied to the flat surface of the A layer side of PET-A in a manner and then dried at 150° C. for 30 seconds to obtain a release film (sample film).
[0509] (Mold release layer composition)
[0510] Main agent: a1; 100 parts by mass
[0511] Cross-linking agent: b1; 3 parts by mass
[0512] Catalyst: c1; 3 parts by mass
[0513] Light stripping agent: e1; 1 part by mass
[0514] Solvent: Toluene; 1000 parts by mass
[0515] MEK: 9000 parts by mass
[0516] [Examples 2-2 to 2-5]
[0517] A film laminate was obtained in the same manner as in Example 2-1 except that the type and amount of the light release agent added were changed as shown in Table 7 below regarding the release layer composition.
[0518] [Comparative Example 2-1]
[0519] A film laminate was obtained in the same manner as in Example 1 except that no light release agent was added to the release layer composition.
[0520] [Comparative Example 2-2]
[0521] In Example 1, except having changed the composition of the release layer into the following release layer composition, it manufactured similarly to Example 1, and obtained the release film (sample film).
[0522] (Mold release layer composition)
[0523] Main agent: a1; 100 parts by mass
[0524] Cross-linking agent: b1; 3 parts by mass
[0525] Catalyst: c1; 3 parts by mass
[0526] Light stripping agent: e4; 1 part by mass
[0527] Solvent: Toluene; 1000 parts by mass
[0528] MEK: 9000 parts by mass [Table 7]
[0529]
[0530] *1 Indicates that heat treatment has not been performed.
[0531] According to the results of this embodiment, it can be confirmed that by making the release layer containing the curable silicone resin thicker, using a light release agent of a specific composition in combination, and setting the elastic modulus to 500 MPa or less, and on the other hand, setting the maximum cross-sectional height (Rt) of the anti-release surface to within a specified range, it is possible to obtain a release film that not only has a light release force but also has low migration and is not prone to adhesion, but nevertheless has good adhesion to the substrate.
[0532] It should be noted that when comparing Comparative Example 1 and each embodiment using the peeling force (normal peeling force) based on the adhesive tape, the lightest type can be peeled lightly to about 60% of Comparative Example 1, and ultra-light peeling can be achieved.
[0533] In contrast, it is known that Comparative Example 1 is at the level of existing products (light release type) and has a large release force to the adhesive layer. Comparative Example 2 has a poor light release effect because the release layer contains a light release agent with a large molecular weight.
[0534] Example 3-1
[0535] The release layer used in Example 1-1 was evaluated for releasability using the adhesive described below. The results are shown in Table 8.
[0536] Adhesive A: 2EHA / BA / HEA=36 / 59 / 5% by mass (elastic modulus: 2.9 MPa, Tg: -59.0°C)
[0537] Adhesive B: 2EHA / HEA / AAc=92.8 / 7 / 0.2 mass % (elastic modulus: 2.7 MPa, Tg: -66.7°C)
[0538] 2EHA; 2-Ethylhexyl acrylate
[0539] BA; Butyl acrylate
[0540] HEA; Hydroxyethyl acrylate
[0541] AAc; acrylic acid
[0542] Example 3-2
[0543] The results are shown in Table 8.
[0544] [Table 8]
[0545]
[0546] It can be seen that the resin layers used in the examples are all easier to peel off than the reference examples (conventional technology).
[0547] Industrial Applicability
[0548] According to the release film of the present invention, a release film that realizes ultra-light peelability and the release characteristics of the release layer are not easily changed due to adhesion can be provided, and its industrial value is high. In addition, the release film of the present invention and the film laminate with the release film have the characteristics of taking into account ultra-light peelability and anti-adhesion, therefore, it is suitable for the use of the change of the release characteristics of the release layer and the deterioration of the appearance of the surface of the resin layer (A), such as the various uses of the touch panel manufacturing of the electrostatic capacitance method, the optical components (polarizing plate, phase difference plate, prism sheet, conductive film, resin film, glass substrate, etc.) used in the liquid crystal display, and the various display components manufacturing such as organic electroluminescent components manufacturing, are also suitable for various adhesive layer protection purposes. It can also be used for foldable display purposes with a soft adhesive layer that is easy to follow the deformation of the bend.
Claims
1. A release film comprising a resin layer (A) on one surface of a substrate film and a resin layer (B) on the other surface, wherein the resin layer (A) comprises a silicone resin release agent and has a thickness of 0.2 to 2.0 μm, and the resin layer (B) comprises a non-silicone resin release agent.
2. The release film according to claim 1, wherein The elastic modulus of the resin layer (A) at 25° C. measured using a nanoindenter device is 500 MPa or less.
3. The release film according to claim 1 or 2, wherein The non-silicone resin-based release agent is at least one selected from the group consisting of wax, a long-chain alkyl-containing compound, and a fluorine compound.
4. The release film according to claim 1 or 2, wherein The content of the release agent in the nonvolatile component of the resin layer (B) is 10 to 70% by mass.
5. The release film according to claim 1 or 2, wherein The resin layer (B) contains substantially no particles.
6. The release film according to claim 1 or 2, wherein The normal peeling force of the resin layer (A) measured by the following evaluation method is 5 g / 25 mm or less, Evaluation method: An acrylic pressure-sensitive adhesive tape "No. 7475" manufactured by Tesa was attached to the resin layer (A) side of the release film, cut into a size of 25 mm x 150 mm, left at room temperature for 1 hour, and peeled at 180° at a tensile speed of 0.3 m / min to measure the peeling force.
7. The release film according to claim 1 or 2, wherein A primer layer is provided between at least one of the resin layer (A) or the resin layer (B) and the base film.
8. The release film according to claim 7, wherein The base coating layer is an antistatic layer.
9. The release film according to claim 7, wherein The primer layer contains the following compounds (A) to (C), (A) a polymer in which a compound containing thiophene or a thiophene derivative is doped with another anionic compound, or a polymer in which a compound containing thiophene or a thiophene derivative has an anionic group and is self-doped, (B) a polyhydroxy compound, (C) One or more compounds selected from the group consisting of polyurethane resins, polyester resins, and acrylic resins.
10. The release film according to claim 1 or 2, wherein The surface resistivity of at least one surface of the resin layer (A) or the resin layer (B) is 1×10 12 Ω / □ or less.
11. The release film according to claim 1 or 2, wherein The substrate film is a polyester film.
12. The release film according to claim 11, wherein The polyester film is composed of three layers.
13. The release film according to claim 1 or 2, wherein The post-pressing re-peeling rate of the resin layer (A) evaluated by the following method is 100% or less, Evaluation method: After affixing an acrylic adhesive tape "No. 7475" manufactured by Tesa to the resin layer (A), the tape was cut into a size of 25 mm x 150 mm, left at room temperature for 1 hour, and peeled at 180° under a tensile speed of 0.3 m / min. The peeling force was recorded as (F1). Next, the laminate was laminated in contact with the resin layer (A) surface, and a press treatment was performed at a temperature of 40° C., a humidity of 90% RH, and a load of 1 MPa for 20 hours. An acrylic adhesive tape "No. 7475" manufactured by Tesa was attached to the treated resin layer (A) surface, and then cut into a size of 25 mm×150 mm. The laminate was left at room temperature for 1 hour, and peeled at 180° under a tensile speed of 0.3 m / min. The peeling force was recorded as (F2). The re-peeling rate after pressing was calculated according to the following formula: Re-peeling rate after pressing (%) = (F2-F1) / F1×100.
14. The release film according to claim 1 or 2, wherein The center line average roughness (Ra(A)) of the surface of the resin layer (A) is 30 nm or less.
15. The release film according to any one of claims 1 or 2, wherein The center line average roughness (Ra(B)) of the surface of the resin layer (B) is 60 nm or less. 16 . A pressure-sensitive adhesive sheet comprising the release film according to claim 1 and another release film via a pressure-sensitive adhesive layer.
17. The adhesive sheet according to claim 16, wherein The adhesive layer is formed of an acrylic adhesive composition.
18. The adhesive sheet according to claim 16 or 17, wherein The adhesive layer has an elastic modulus of 6.0 MPa or less at 25°C.
19. The adhesive sheet according to claim 16 or 17, wherein The adhesive layer contains 2-ethylhexyl acrylate and / or butyl acrylate. 20 . The adhesive sheet according to claim 16 or 17 , which is used for an optical transparent adhesive sheet.
21. The release film according to claim 1 or 2, which is used for a display.
22. The release film according to claim 1 or 2, which is used for a foldable display.
23. A method for using an adhesive sheet, wherein: In the pressure-sensitive adhesive sheet according to any one of claims 16 to 19, a surface of the pressure-sensitive adhesive layer exposed after peeling off the other release film is bonded to an optical member.
24. The method for using the adhesive sheet according to claim 23, wherein: The optical component is a polarizing plate or a touch sensor.
Citation Information
Patent Citations
New polythiophene dispersion and its preparation
JP1995090060A
Release film
JP2004255704A
Mold release film excellent in releaseability
JP2016165825A
Release film with excellent releasability
JP2017061081A
Release liner and double-faced tape using it
JP2003080638A